Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

Clinical outcomes of patients with brain metastases from primary esophageal cancer - Bianca Nolde-Lopez; Christina K. Cramer; Scott Isom; Anthony Naquin; Caio M.S.P. Rocha Lima; Ravi K. Paluri; Jimmy Ruiz; Fei Xing; Christopher T. Whitlow; Stephen B. Tatter; Adrian W. Laxton; Jaclyn J. White; et al. (Next Research, 2026)

Adjoint sensitivity analysis of nonstandard objective functions - Wee Hao Ng; Christopher R. Myers; Scott H. McArt; Stephen P. Ellner (Mathematical Biosciences, 2026)

Detection of seizurogenic compounds in human and rat neurons in vitro: A multi-laboratory, multi-model assessment - Ruth Roberts; Ksenia Blinova; Coby Carlson; Matthew Cato; Katherine Czysz; Tromondae K. Feaster; Xiaobo Han; Yuto Ishibashi; Yasunari Kanda; Mohamed Kreir; Paul Levesque; Norimasa Miyamoto; et al. (NeuroToxicology, 2026)

Connecting ambient toxicity testing with community-level responses of benthic macroinvertebrates in an impacted stream in East Tennessee, USA - Louise M. Stevenson; Paul G. Matson; Peyton C. Marcum; Nikki J. Jones; Scott C. Brooks; Trystan Bordeau; Allison M. Fortner; Natalie A. Griffiths; Christopher R. DeRolph; R. Trent Jett; Michael W. Jones; Peijia Ku; et al. (Journal of Environmental Management, 2026)

Association between ambient air pollution and colorectal cancer risk: The Multiethnic Cohort Study - Ugonna Ihenacho; Chiuchen Tseng; Jun Wu; Scott Fruin; Timothy V. Larson; Salma Shariff-Marco; Loïc Le Marchand; Daniel O. Stram; Brian Z. Huang; Lynne R. Wilkens; Christopher A. Haiman; Beate Ritz; et al. (Environmental Research, 2026)

Western Sandpiper ( Calidris mauri ) use of intertidal biofilm in freshwater and marine influenced mudflats during migratory stopover - Scott H. Walters; Christopher G. Guglielmo; Mark C. Drever; Scott A. Flemming; Mark Maftei; Keith A. Hobson (Isotopes in Environmental and Health Studies, 2026)

Springshed management and rural water Security: Seen and unseen infrastructure in the Eastern Himalaya - Abriti Moktan; Christopher A. Scott; Sarala Khaling; Veena Srinivasan; Rinan Shah (Water Security, 2026)

Past, present and future of the indus water treaty: implications for transboundary water governance challenges and modernization prospects - Tejal S. Shirsat; Lara B. Fowler; Christopher A. Scott (Water Security, 2026)

Tidally driven topographic eddies exploited by manta feeding aggregations - Harvey Cairns; Daniel Conley; Christopher Stokes; Tim Scott; Phil Hosegood (Estuarine, Coastal and Shelf Science, 2026)

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

Correction: Genome‑wide association study of soybean germplasm derived from modern Canadian and Chinese soybean cultivars to identify novel genes conferring soybean cyst nematode resistance - Scott Moore; Owen Wally; Albert Tenuta; Mohsen Yoosefzadeh Najafabadi; Christopher Grainger; Milad Eskandari; Istvan Rajcan (Theoretical and Applied Genetics, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Mesoscale eddies in the subpolar North Atlantic: their ecological importance and conservation significance - Lea-Anne Henry; Jason Cleland; Anna Gebruk; René Schubert; Alice Della Penna; Peter Gaube; Christian Mohn; Brynn Devine; Arne Biastoch; Camille M.L.S. Pagniello; Keno Ferter; George Wolff; et al. (Progress in Oceanography, 2026)

Navigating urban ecology: Conceptual and methodological insights - Ian MacGregor‐Fors; Christine C. Rega‐Brodsky; D. Johan Kotze; J. Scott MacIvor; Amy K. Hahs; Marco Moretti; Nicholas S. G. Williams; Christopher A. Lepczyk; Kirsten Jung; Madhusudan Katti; Sonja Knapp; Frank A. La Sorte; et al. (Ecology, 2026)
Since its consolidation as a sub‐discipline of ecology in the late 1990s, urban ecology has grown substantially, enhancing our understanding of how urbanization shapes biodiversity and how biodiversity adapts to urbanization. Inherently interdisciplinary in its scope and application, urban ecology is rooted in multiple theoretical and methodological foundations, potentially making the field overwhelming for newcomers as the key literature is scattered across multiple disciplines. Drawing on the collective expertise of editors and reviewers, we attempt to address common pitfalls noted in studies of biodiversity within urban ecosystems and suggest action items for both the new and experienced urban ecologist. Here, we present key concepts for framing hypothesis‐based urban biodiversity research questions, conceptualizing urban settings, accounting for spatial and temporal scales, selecting study systems and meaningful explanatory variables for research questions, and recognizing the social‐ecological nature of urban systems. We offer insights and examples, emphasizing the importance of rigorous urban ecological research without imposing constraints on innovation.

Goals and trends in space exploration: An overview of the panel on exploration sessions at the committee on space research general assembly 2024 - André Galli; Heather Smith; Michel Blanc; Bernard Foing; Hélène Boithias; Scott J. Bolton; Soyoung Chung; Athena Coustenis; Eric Dautriat; Jean-Pierre de Vera; Peter Doran; François Dubrulle; et al. (Life Sciences in Space Research, 2026)

Genome-wide association study of soybean germplasm derived from modern Canadian and Chinese soybean cultivars to identify novel genes conferring soybean cyst nematode resistance - Scott Moore; Owen Wally; Albert Tenuta; Mohsen Yoosefzadeh Najafabadi; Christopher Grainger; Milad Eskandari; Istvan Rajcan (Theoretical and Applied Genetics, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Distributed optical fibre sensing in physical oceanography: emergence and future prospects - Alberto C. Naveira Garabato; Carl P. Spingys; Andrew J. Lucas; Tiago S. Dotto; Christian T. Wild; Scott W. Tyler; Ted A. Scambos; Christopher B. Kratt; Giuseppe Cappelli; Ethan F. Williams; Mariona Claret; Hannah E. Glover; et al. (Ocean Science, 2026)
Distributed optical fibre sensing (DOFS) is a technology that enables continuous, real-time measurements of a range of environmental parameters along the length of a fibre optic cable. In this article, we review the recently emerged applications of DOFS techniques in physical oceanography and offer a perspective on the technology's potential for future growth within the field. The introduction of DOFS to physical oceanography is contextualised with a brief history of the technology, which spun off primarily from the use of seafloor-laid optical fibres for telecommunications purposes. The key components and underpinning physics of a DOFS system are outlined and, on their basis, the suite of variables that are observable with DOFS are discussed. The implementation factors of DOFS, which include trade-offs between measurement accuracy and spatio-temporal resolutions and ranges, are also examined. The physical oceanographic applications of DOFS to date are then illustrated with case examples of four distinct DOFS techniques: distributed temperature sensing (DTS), which can provide ocean temperature observations; distributed static strain sensing (DSS) and distributed acoustic sensing (DAS), which are sensitive to temperature, cable strain and strain-associated variables, such as pressure and ocean velocity; and ultra-long-range observations of ocean currents with optical interferometry. The forthcoming prospects of DOFS in physical oceanography are considered, and are proposed to include new fibre optic-based approaches to sense ocean salinity and measure through the water column. We conclude with reflections on the future role of DOFS within the Global Ocean Observing System, and highlight the opportunities provided by the existing world-wide network of seafloor-laid optical fibres.

Associations of self-reported sleep quality and duration with dietary eating behaviours: a cross-sectional study of 27,263 UK adults - Scott A. Willis; Arwa Alruwaili; Iuliana Hartescu; Kevin Deighton; Christopher Goodwin; Joseph Henson; Alice E. Thackray; David J. Stensel; James A. King (Appetite, 2026)

Emerging hydrogen spot indices: Price taker or maker? - Chaewon Kim; Scott M.R. Mahadeo; Keiron P. Roberts; Christopher R. Jones (Journal of Environmental Management, 2026)

Understanding Patterns and Drivers of Changing Sectoral Economic Water Use in Scotland - Maria Clemens; Scott McGrane; Christopher J. White (Water Resources Management, 2026)
Understanding economic water use remains challenging due to limited data availability and confidentiality constraints that restrict the robust assessment of sectoral patterns. This study presents the first publicly available national dataset for Scotland that integrates abstraction and network-supplied water volumes across 81 economic sectors, enabling consistent sectoral water-use assessment and ranking of major contributors to national demand. An integrated, diagnostic analytical approach was applied to capture both short- and long-term water-use behaviour. Short-term analysis captures monthly water-use dynamics, including recurring seasonal patterns and responses to extreme events, while long-term results describe sectoral developments and the drivers shaping them. Sectoral profiles combining these observations with qualitative evidence reveal three dominant driver types: hydro-climatic, economic-structural, and behavioural-operational. These profiles were used to derive indicative sectoral estimates for 2025, reflecting heterogeneous and evolving influences over time. Gross Value Added (GVA) provides contextual information but has only limited explanatory power, underscoring the need for sector-specific interpretation. Differentiated approaches therefore provide a more realistic basis for water-use assessment than uniform assumptions, particularly where demand is heterogeneous. The study delivers a sector-level overview of economic water use in Scotland, supporting more transparent monitoring and more robust interpretation of future demand. The dataset further offers insights into water-intensive activities common across many economies. This driver-based classification offers transferable analytical logic for regions with fragmented water-use data and evolving economic structures, supporting more targeted monitoring and realistic demand assessment.

Automating microalgal raceway pond operations using real-time spectroradiometric monitoring - Song Gao; Christopher Katinas; Jerilyn A. Timlin; Thomas A. Reichardt; Scott Edmundson; Michael Huesemann (Algal Research, 2026)

Earthworm assemblages in the Eastern and Midwestern United States and the legacy of glaciation - Timothy S. McCay; Laurel J. Anderson; Christopher P. Bloch; Abigail E. Cahill; Sandra L. Cooke; Benjamin J. Dolan; Kathryn M. Flinn; Danielle Garneau; Nathaniel J. Hains; Kristy Hopfensperger; Mary Beth Kolozsvary; Carol Mankiewicz; et al. (Biological Invasions, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Effects of Forest Management and Land Use Change on Soil Carbon in the US Gulf Coastal Plain - Lucas E. Nave; Kendall DeLyser; Grant M. Domke; Scott M. Holub; Adrienne B. Keller; Darren Miller; Kevin A. Solarik; Erik Schilling; Jason Vogel; Christopher W. Swanston (Journal of Forestry, 2026)
The US Gulf Coastal Plain is a region of diverse forests and management systems and dynamic land use changes. These drivers affect carbon (C) stocks at ecosystem to regional scales, in turn affecting processes such as forest regeneration, hydrologic and biogeochemical cycling, and social and economic systems. We quantified land use change and forest management effects on C stocks in the Gulf Coastal Plain, focusing on soils, using two complementary approaches: meta-analysis of published literature and analysis of forest inventory data. Land use change had larger effects than forest management on soil C stocks at all scales. The direction and magnitude of change in soil C stocks differed among various types of land use change. From a regional perspective, the most important significant changes were those occurring with transfers between agricultural and forested land uses, though less extensive land uses also registered significant changes (e.g., wetland restoration, mine reclamation). Management of continuously forested land had subtler effects, which were focused on aboveground biomass and soil organic horizons. Organic horizons were consistently diminished by prescribed fire and may be reduced by harvesting, though evidence is limited for the latter, and declines are temporary in both cases. Aboveground activities intended to increase stand re-establishment and tree growth, such as competing vegetation control and fertilization, are at least compatible, and potentially synergistic with C storage in belowground pools. Overall, our results demonstrate how forest management can support forest C management and offer quantitative insights into specific management activities to aid researchers, policymakers, and practitioners.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Integration of Indigenous practices into fisheries legislation: Obstacles and opportunities for the maramataka (Māori lunar calendar) - Louise Bennett-Jones; Christopher D. Hepburn; Brendan Flack; Nigel J. Scott; Gaya Gnanalingam (Marine Policy, 2026)

On the path to regenerative nature-based tourism in Canada? Insights from the legacy of COVID-19 on Canadians’ travel behaviours - Brooklyn Rushton; Christopher J. Lemieux; Daniel J. Scott; Michelle Rutty (Journal of Outdoor Recreation and Tourism, 2026)

Influences of Structural and Species Diversity on Forest Resistance to Drought - Erin T. H. Crockett; Qinfeng Guo; Jeff W. Atkins; Ge Sun; Kevin M. Potter; Jennifer K. Costanza; Scott V. Ollinger; Christopher W. Woodall; Steven McNulty; Carl Trettin; Justin Holgerson; Jingfeng Xiao (Ecology Letters, 2026)
Biodiversity can enhance forest resistance to drought, but the forms of diversity involved and conditions under which diversity confers resistance remain unclear. We used Forest Inventory and Analysis (FIA) plot data to examine whether four variables—structural richness (variation in tree heights, stand density, canopy cover and/or spatial heterogeneity), species richness (number of tree species), structural evenness and species evenness—are associated with the resistance of net primary productivity to drought and whether these relationships change with drought severity and by ecoregion. Structural richness was positively associated and species evenness was negatively associated with resistance, but the strength of these relationships varied by ecoregion. Relationships between structural richness and resistance and between species evenness and resistance became stronger under more severe droughts, supporting the stress gradient hypothesis. Forest managers cannot readily change abiotic conditions but could increase structural richness and select certain species to enhance forest resistance to drought.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Which trees matter most? The role of private garden trees and woodland cover for 3–30-300 success in seven English cities - Eleanor S. Smith; Christopher Fleet; Arjan S. Gosal; Stuart King; Hannah Walker; Ian Willey; Catherine E. Scott (Urban Forestry & Urban Greening, 2026)

Niche partitioning and limited mobility characterise Middle Pleistocene kangaroos from eastern Australia - Christopher Laurikainen Gaete; Scott Hocknull; Clement P. Bataille; Andrew M. Lorrey; Katarina M. Mikac; Rochelle Lawrence; Anthony Dosseto (Quaternary Science Reviews, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Hearing preservation and restoration surgery in NF2-related schwannomatosis - Christopher G. Wood; Nathan Huey; Christine Carter; Nathaniel Truong; Fred G. II Barker; Scott R. Plotkin; D. Bradley Welling (Familial Cancer, 2026)

Metagenomics in the diagnosis of pneumonia: a systematic review - Samuel Quarton; Alana Livesey; Charlotte Jeff; Christopher Hatton; Celine Hsi Chen; Aaron Scott; Dhruv Parekh; David Thickett; Alan McNally; Elizabeth Sapey (Infectious Diseases, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Biomechanical Analysis of the Effects of Knee Savers on Knee Joint Loading During High Knee-Flexion Tasks - Liying Zheng; John Z. Wu; Kevin D. Moore; Ashley L. Hawke; Robert E. Carey; Christopher M. Warren; Scott P. Breloff (Annals of Biomedical Engineering, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Correction: Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)

Near‐seabed sediment dynamics and fluxes on Chatham Rise, the effects of seabed disturbance, and implications for deep‐sea bottom trawling and seabed mining - Scott D. Nodder; Christopher A. Eager; Joe O’Callaghan; Daniel Leduc; Sam Davidson; Stacy Deppeler; Grace Frontin‐Rollet; Peter Gerring; Sarah Searson; William Quinn; Steve George; Ron Ovenden; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
Anthropogenic impacts are increasingly affecting deep‐sea environments, including seafloor sediment disturbances by bottom trawling and seafloor mining. Fieldwork in the ‘Resilience Of Benthic Ecosystems to Sedimentation’ (ROBES) project were conducted in 2018–2020 on the 400 m‐deep Chatham Rise crest, eastern Aotearoa New Zealand. Water column turbidity data, sediment traps on near‐seabed moorings and benthic landers and surficial sediments from multi‐corers provided baseline and post‐impact information following an artificially induced seafloor disturbance event in June 2019 using a modified harrow plough in and around an elongated bathymetric depression, designated as the ‘Butterknife’. During the disturbance, total mass and particulate organic carbon (POC) near‐bed fluxes were elevated above long‐term fluxes (2018–20). Long‐term 2018–19 fluxes were generally less than in 2019–20, driven by interannual oceanographic variations. These results, coupled with 50–100 m‐thick benthic boundary layers, suggest that lateral advection is a dominant process in the resuspension and redistribution of seafloor sediments on the rise. Further research is required to better understand the longer term dynamics of particle transport and deposition in response to human activities, such as bottom trawling or proposed phosphorite seafloor mining, especially in bathyal environments, such as the Chatham Rise.

Effects of an experimental in situ seabed disturbance on deep‐sea benthic ecosystem function and macro‐infaunal community structure on the Chatham Rise, Southwest Pacific - Rachel Hale; Daniel Leduc; Campbell Murray; Ashley A. Rowden; Scott D. Nodder; Chris Eager; Rob Stewart; Christopher W. Hickey; Conrad Pilditch; Malcolm R. Clark (New Zealand Journal of Marine and Freshwater Research, 2025)
Expansion of extractive industries to deep‐sea environments will lead to increased stresses on seafloor ecosystems. We examined changes in environmental parameters following direct and indirect experimental benthic disturbance using a modified plough on the Chatham Rise (∼450 m water depth), Aotearoa/New Zealand. Measurements included sediment community oxygen consumption (SCOC), nutrient fluxes, macro‐infauna community composition, and sediment organic carbon (C) and nitrogen (N) content. We observed an increase in SCOC immediately after the disturbance, alongside a decrease in macro‐infauna abundance, biomass, species richness, and diversity, and an increase in sediment C:N. One‐year after the disturbance, SCOC and sediment C:N ratios were similar to that of pre‐disturbance levels, while macro‐infauna abundance and biomass were greater. We observed a shift in the community structure at directly disturbed sites one‐year post‐disturbance with decreased biomass of Polychaeta and increased biomass of Ophiuroidea. No changes were observed in sediment nutrient fluxes. Our study indicates the Chatham Rise benthic ecosystem was initially negatively affected by the disturbance, but the recovery of many parameters after one‐year shows the potential resilience of the ecosystem. Compared to many proposed deep‐sea resource extraction sites the Chatham Rise experiences a relatively high‐level of anthropogenic and natural disturbance which may explain the relatively rapid recovery. Seafloor resilience to human disturbances and recovery from impacts will depend on local environmental conditions that need to be evaluated by environmental impact assessments. This knowledge will be key to predicting and mitigating disturbance impacts. While the Chatham Rise is relatively well studied many other regions, including those planned for extractive activities, lack the information needed.

Congener Conflict: Invasive Barred Owl Landscape Use Across the Range of the Northern Spotted Owl - Julianna M. A. Jenkins; Natalie M. Rugg; Raymond J. Davis; Scott A. Gremel; Aaron Henderson; Edward Henson; Mark Higley; Holly D. Horan; Christopher McCafferty; Thomas Munger; David Press; Suzanne Reffler; et al. (Journal of Biogeography, 2025)
Aim To map the probability of landscape use of invading barred owls ( Strix varia ) across the range of the threatened northern spotted owl ( S. Occidentallis Caurina ) in the Pacific Northwest, USA , identifying environmental drivers of barred owl landscape use to inform targeted management interventions. Location Forests of the Pacific Northwest, USA. Taxon Barred Owl ( Strix varia ). Methods We deployed 4081 autonomous recording units ( ARUs ) within 1027 randomly selected long‐term monitoring sites consisting of 5‐km 2 hexagons in 2023. We processed audio recordings using convolutional neural networks to detect vocalisations. We applied single‐season occupancy models at both ARU station and hexagon scales to estimate barred owl landscape use and assess associations with environmental variables. Using top models, we mapped barred owl landscape use across the full US range of the northern spotted owl, an umbrella species for conservation of the pacific northwest old‐growth forest community. Results Barred owls were widely detected, with naïve occupancy at 86.8% at the 5‐km 2 hexagon scale. We observed regional variation, with the highest landscape use in the Oregon Coast region and lower landscape use in California regions and the Washington Eastern Cascades. Landscape use was positively associated with mature forest characteristics at both broad and fine scales and negatively associated with elevation and climatic water deficit. Cumulative detection probability exceeded 90% after 2 weeks at the hexagon scale and 4 weeks at the station scale, providing guidance for future barred owl monitoring efforts. Main Conclusions Our study reveals extensive, but not ubiquitous, barred owl distribution across the range of the northern spotted owl. The findings offer a decision‐support framework for prioritising targeted management actions, particularly in regions with lower rates of barred owl landscape use. The integration of passive acoustic monitoring and AI‐based detection demonstrates a scalable approach for invasive species monitoring and conservation planning to meet management objectives in dynamic forest landscapes.

Predictions of southern migration timing in coastal sharks under future ocean warming - Maria H. Manz; Oliver N. Shipley; Robert M. Cerrato; Robert E. Hueter; Alisa L. Newton; John P. Tyminski; Bryan R. Franks; Tobey H. Curtis; Christopher Fischer; Joshua P. Zacharias; Christopher Scott; Keith J. Dunton; et al. (Conservation Biology, 2025)
Projected redistribution of marine species due to ocean warming may undermine current conservation efforts. Yet, there have been few studies on how ocean warming may alter migration timing. Across 5 years of acoustic telemetry data (2018–2022), we determined environmental drivers of southward migration timing for 6 migratory shark species from summer habitats in the Northwest Atlantic Ocean. We then forecasted how migratory timing from 3 regions, between the New England shelf and Mid‐Atlantic Bight, would respond under future sea surface temperatures (SSTs). Photoperiod and SST were strong predictors of southern migration in sharks, but the strength of these effects varied latitudinally. Overall, we found delayed departure dates from summer habitats under future elevated SSTs, indicating prolonged residency in northern habitats (median = ∼12 days). Sandbar sharks ( Carcharhinus plumbeus ) exhibited the largest delay in the onset of southern migrations (median = 29 days), whereas sand tiger sharks ( Carcharias taurus ) and white sharks ( Carcharodon carcharias ) exhibited the smallest delay (median = 1 day). Delays in migration timing of coastal shark species may alter local ecosystem dynamics and challenge current management strategies. These findings illustrate the utility of collaborative data‐sharing networks to expand understanding of broadscale animal movements and contribute to effective species management under a changing climate.

Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)
Introduction Species distribution models (SDMs) are increasingly used in fisheries science to understand species’ spatial patterns and improve stock assessments. Method This study developed SDMs for eulachon smelt ( Thaleichthys pacificus ), a threatened, demersal forage fish often caught as bycatch in the United States West Coast ocean shrimp trawl fishery. Using ten years of observer data (2012–2021, n=19,749 with 25.4% being zeros), the study assessed the influence of static (e.g., substrate) and dynamic (e.g., ocean temperature, currents) environmental variables on eulachon abundance. Results The best-performing SDM included near-bottom temperature and current data, outperforming SDMs using only surface variables. Eulachon abundance peaked at ~150 m depth, especially over gravel substrates, and during nighttime. Although none of the SDM-based abundance indices significantly correlated with the Columbia River stock assessment index, bottom-based SDMs showed stronger alignment with the stock assessment (R=0.61, p=0.08 & R=0.62, p=0.07). Discussion Management implications are significant. Rock habitats were associated with higher eulachon bycatch, and vessels can use bottom-typing tools to avoid them. Also, delaying the season opener could reduce bycatch, as eulachon catch was reduced by 0.0109 mt per trawl over the interquartile range of day of the year. These findings can inform Best Management Practices (BMPs), which have historically led to regulatory changes such as the adoption of excluder grates and LED lights. Overall, incorporating near-bottom oceanographic data greatly enhanced predictive performance, especially for demersal species like eulachon. These mechanistic SDMs can be projected forward, aiding future management amid changing ocean conditions. While some discrepancies remain, this approach offers promising insights for adaptive fishery management and conservation of imperiled species like eulachon.

Mitochondrial dysfunction drives age-related degeneration of the thoracic aorta - Arjune S. Dhanekula; Benjamin R. Harrison; Gavin Pharaoh; Aurora Mattson-Hughes; Stefano Tarantini; Rudolph Stuppard; Scott C. DeRoo; Christopher R. Burke; Billiana Hwang; Jay D. Pal; Michael S. Mulligan; David J. Marcinek (GeroScience, 2025)

Evaluating impacts of cerium oxide nanoparticles on natural assemblages of diatom-dominated phytobenthos and phytoplankton in river water - Marian L. Yallop; Hannah Masani; Christopher Jones; Yunyang Wang; Thomas B. Scott; Anna Regoutz; Miguel Gomez-Gonzalez; Alexander E. Porter (Science of The Total Environment, 2025)

Comparing Navcam dust devil detections to transient daytime convective vortex signatures in REMS pressure and ultraviolet data - Emily L. Mason; Scott D. Guzewich; Christopher Edwards; Álvaro Vicente-Retortillo; Daniel Viúdez-Moreiras (Icarus, 2025)

Assessing U.S. Media’s Reaction to a Suggested Terminology Shift from “Accident” to “Incident” in News Reports of Childhood Agricultural Injury: A Pilot Study - Christopher P. Benny; Jakob Hanschu; Scott Heiberger; Barbara C. Lee; Bryan Weichelt (Journal of Agromedicine, 2025)

Effects of doxycycline on prepatent and patent infections of Brugia pahangi in dogs and observations on the growth and survival of L3 in jirds and dogs - John W. McCall; Laura Kramer; Claudio Genchi; Jorge Guerrero; Michael T. Dzimianski; Abdelmoneim Mansour; Scott McCall; Ben Carson; Christopher C. Evans (Veterinary Parasitology, 2025)

One for all and all for one health: Harmonizing SARS-CoV-2 wastewater surveillance results across a laboratory network - Alex H.S. Chik; Christopher Adam; Jane J.Y. Ho; Taylor Aris; Eric J. Arts; R. Stephen Brown; David Bulir; Ryland Corchis-Scott; Christopher T. DeGroot; Robert Delatolla; Philip Dennis; Hadi A. Dhiyebi; et al. (Science of The Total Environment, 2025)

The HydroBio Dataset: a new data resource for evaluating existing and potential hydropower capacity and freshwater biodiversity in the conterminous United States - Bryan B. Bozeman; Paul G. Matson; Christopher R. DeRolph; Scott T. DeNeale (Journal of Environmental Management, 2025)

Chronic arsenic exposure and hsa-miR-186 overexpression causes transcriptome-wide differential alternative splicing contributing to skin carcinogenesis in human HaCaT cell line - Mayukh Banerjee; Jared L. Scott; Angeliki Lykoudi; Jae Y. Hwang; Juw W. Park; J. Christopher States (Archives of Toxicology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

DNA damage response inhibition is an early event in cadmium-induced breast carcinogenesis - Alexandra N. Nail; Ashley V. Chavez; Aliyah N. Bailey; Mayukh Banerjee; Jared L. Scott; Shelia D. Thomas; J. Christopher States (Toxicology and Applied Pharmacology, 2025)

The discovery and preclinical pharmacology of JNJ-10450232 (NTM-006), a centrally penetrant, non-opioid structural analog of acetaminophen with comparable analgesic and anti-pyretic properties but no evidence of hepatotoxicity - Christopher M. Flores; John R. Carson; Ellen E. Codd; Scott L. Dax; Edwin K. Kuffner; Paul L. Stahle; Robert A. Neff; Gary E. Eichenbaum (Regulatory Toxicology and Pharmacology, 2025)

Development and characterization of an aerosol-generated multi-method analytical particle test material - Lorianne R. Shultz-Johnson; Benjamin T. Manard; Rachel Bergin; Dominic Piedmont; Jordan S. Stanberry; Hunter B. Andrews; Brian W. Ticknor; Mehmet Topsakal; Andrew Kiss; Gage Green; Matthew Wellons; Spencer Scott; et al. (Journal of Aerosol Science, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

Legacy effects of four decades of insecticide applications on contemporary riverine benthic macroinvertebrates - Scott Sugden; Amy B. White; Jennifer Lento; Joshua Kurek; Ilya Dimitrovas; Sandra Emry; Xiaotian Hua; Moira M. Ijzerman; Karen A. Kidd; Katlyn LM. Morrow; Jessica E. Ollinik; Laura Schnell; et al. (Environmental Pollution, 2025)

Magnesian-suite volcanism and ancient crust building on the Moon 4.25 billion years ago - Christopher Yen; Cécile Deligny; Bradley Jolliff; Alexander Nemchin; Paul Carpenter; Martin Whitehouse; Renaud Merle; Ryan Ogliore; Jeremy Kent; Ryan Zeigler; Juliane Gross; Scott Eckley; et al. (Earth and Planetary Science Letters, 2025)

Managing River Low Flows to Enhance Instream Vegetation Recruitment - Christopher S. Jones; Scott A. McKendrick; Lyndsey M. Vivian; Piyumi Wijepala; Bryan Mole; Darren White; Joe Greet (Environmental Management, 2025)
River regulation has reduced natural flow peaks in rivers globally, and in some cases has also reduced the occurrence of low-flows that expose the riverbed. Minimum low-flows are commonly mandated for temperate managed waterways in summer to maintain water quality and aquatic habitat for flora and fauna, at levels which prevent riverbed exposure. Very low flows that allow partial riverbed exposure may have many important roles in naturally impermanent waterways, including promoting plant recruitment. We conducted an in-situ field experiment in a regulated river by drawing down flows for two weeks in austral autumn to facilitate plant recruitment from the riverbed. We also conducted a concurrent ex-situ experiment in controlled conditions using sediment samples from field plots and subjecting them to exposure and inundation treatments. Two-week exposure of riverbed sediments was sufficient to trigger the germination of thousands of flood-tolerant riverine plants in both the in-situ and ex-situ experiments, but aquatic plants showed little response. Terrestrial plant seedlings were uncommon within the river-bed substrate. Seedlings were tolerant of early re-inundation but prolonged inundation resulted in senescence and mortality for non-aquatic plants. Very low flows in rivers for at least two weeks may facilitate recruitment of flood-tolerant riverine plants but the event timing and re-inundation regime will influence the likelihood of successful plant establishment. While there are potential risks for some aquatic taxa by implementing very low flows, this needs to be weighed against the potential benefits of riverbed exposure for promoting important biotic processes including plant recruitment.

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Subcortical white matter hyperintensities and motor function in parkinson’s disease: findings from the ONDRI study - Daniela Cristina Carvalho de Abreu; Frederico Pieruccini-Faria; Anthony E. Lang; Benjamin Cornish; William McIlroy; Mandar Jog; Mario Masellis; Joel Ramirez; Christopher Scott; Sean Symons; Sandra E. Black; Stephen R. Arnott; et al. (GeroScience, 2025)

Changes in GEDI-based measures of forest structure after large California wildfires relative to pre-fire conditions - Matthew L. Clark; Christopher R. Hakkenberg; Tim Bailey; Patrick Burns; Scott J. Goetz (Remote Sensing of Environment, 2025)

Confronting the interconnection of chemical pollution and climate change - Simona A. Bălan; Saskia K. van Bergen; Ann Blake; Topher Buck; Scott Coffin; Jamie C. DeWitt; Gretta Goldenman; Frank A. von Hippel; Sophia von Hippel; Christopher P. Leonetti; David Rist; Martin Scheringer; et al. (Environmental Innovation and Societal Transitions, 2025)

Towards environmental justice: A framework and strategic approach for implementing community based participatory research in the earth and environmental sciences - Alexis M. Wilson; Emily Polk; Christopher B. Field; Scott Fendorf (Environmental Science & Policy, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evaluation of six sugar kelp crosses selected for high yield at three Northeastern US farms - Sara T. Gonzalez; Yaoguang Li; Margaret Aydlett; David Bailey; Hadley Kerr; Michael Doall; Christopher J. Gobler; Michael Chambers; Jean-Luc Jannink; Charles Yarish; Scott Lindell (Aquaculture, 2025)

Coproducing water-energy-food Nexus actionable knowledge: Lessons from a multi-actor collaborative learning school in Uganda, East Africa - Ida N.S. Djenontin; Bassel Daher; Jacob W. Johnson; Kenan Adule; Birhanu K. Hishe; Patience Kekirunga; Vanessa King; Emma Gaalaas Mullaney; Patience Nimushaba; Michael G. Jacobson; Annette Huber-Lee; Ellen J. Kayendeke; et al. (Environmental Science & Policy, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

The AGN-201 Digital Twin: A test bed for remotely monitoring nuclear reactors - Ryan Stewart; Eduardo Treviño; Ashley Shields; Kolton Heaps; John Darrington; Quinton Williams; Chad Pope; Johnathan Scott; Benjamin Baker; Jaden Palmer; Benoni Vainqueur; Todd S. Palmer; et al. (Annals of Nuclear Energy, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Evaluating rainfall and graupel retrieval performance of the NASA TROPICS pathfinder through the NOAA MiRS system - John Xun Yang; Yong-Keun Lee; Shuyan Liu; Christopher Grassotti; Quanhua Liu; William Blackwell; Robert Vincent Leslie; Tom Greenwald; Ralf Bennartz; Scott Braun (Remote Sensing of Environment, 2025)

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Land use change and forest management affect soil carbon stocks in the central hardwoods, U.S. - Lucas E. Nave; Kendall DeLyser; Grant M. Domke; Scott M. Holub; John M. Kabrick; Adrienne B. Keller; Patricia Leopold; Matthew P. Peters; Kevin A. Solarik; Christopher W. Swanston (Geoderma Regional, 2025)

Resistance exercise training in older men reduces ATF4-activated and senescence-associated mRNAs in skeletal muscle - Zachary D. Von Ruff; Matthew J. Miller; Tatiana Moro; Paul T. Reidy; Scott M. Ebert; Elena Volpi; Christopher M. Adams; Blake B. Rasmussen (GeroScience, 2025)
Sarcopenia increases the risk of frailty, morbidity, and mortality in older adults. Resistance exercise training improves muscle size and function; however, the response to exercise training is variable in older adults. The objective of our study was to determine both the age-independent and age-dependent changes to the transcriptome following progressive resistance exercise training. Skeletal muscle biopsies were obtained before and after 12 weeks of resistance exercise training in 8 young (24 ± 3.3 years) and 10 older (72 ± 4.9 years) men. RNA was extracted from each biopsy and prepared for analysis via RNA sequencing. We performed differential mRNA expression, gene ontology, and gene set enrichment analyses. We report that when comparing post-training vs pre-training 226 mRNAs and 959 mRNAs were differentially expressed in the skeletal muscle of young and older men, respectively. Additionally, 94 mRNAs increased, and 17 mRNAs decreased in both young and old, indicating limited overlap in response to resistance exercise training. Furthermore, the differential gene expression was larger in older skeletal muscle. Finally, we report three novel findings: 1) resistance exercise training decreased the abundance of ATF4-activated and senescence-associated skeletal muscle mRNAs in older men; 2) resistance exercise-induced increases in lean mass correlate with increased mRNAs encoding mitochondrial proteins; and 3) increases in muscle strength following resistance exercise positively correlate with increased mRNAs involved in translation, rRNA processing, and polyamine metabolism. We conclude that resistance exercise training elicits a differential gene expression response in young and old skeletal muscle, including reduced ATF-4 activated and senescence-associated gene expression.

Virginia Heat Watch: Collaboration to assess climate vulnerability at local to regional scales - Todd R. Lookingbill; Karin P. Warren; J. Christopher Haley; Elizabeth G. Malcolm; Lisa Jordan Powell; Scott M. Starr; Sarah Melissa Witiak; Michael J. Wolyniak; Beth Zizzamia (Urban Climate, 2025)

Strain rates recorded in the perimeter-area relationship of recrystallized quartz aggregates from the Sandhill Corner shear zone, Maine, USA - Erik K. Anderson; Won Joon Song; Scott E. Johnson; Christopher C. Gerbi (Journal of Structural Geology, 2025)

Using δ65Cu and δ34S to determine the fate of copper in stream waters draining porphyry mineralization: Implications for exploration targeting - James A. Kidder; Christopher E. Beckett-Brown; Alexandre Voinot; Zhaoping Yang; Pierre Pelchat; Duane C. Petts; Matthew Polivchuk; John B. Chapman; Scott Casselman; Matthew I. Leybourne (Chemical Geology, 2025)

Autonomous anomaly detection of proliferation in the AGN-201 nuclear reactor digital twin - Eduardo Treviño; Ashley Shields; Ryan Stewart; John Darrington; Jonathan Scott; Chad Pope; Christopher Ritter (Annals of Nuclear Energy, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Estimating the density of urban trees in 1890s Leeds and Edinburgh using object detection on historical maps - Eleanor S. Smith; Christopher Fleet; Stuart King; William Mackaness; Hannah Walker; Catherine E. Scott (Computers, Environment and Urban Systems, 2025)

Twenty-Two-Year Study of the Spread and Impact of Hemlock Woody Adelgid and Elongate Hemlock Scale in Southwest Virginia - Thomas J. McAvoy; Ryan Mays; Mohamed Salem; Lori Chamberlin; Rusty Rhea; Christopher Asaro; Scott M. Salom (Journal of Forestry, 2025)
This 22-year study examined the impact and dispersal of the hemlock woolly adelgid (HWA) and the elongate hemlock scale at 67 sites in southwest Virginia. A hemlock stand health index was based on percent foliage density, live crown ratio, live branches, live tips, new foliage, and live trees at each site. At the beginning of the study, hemlock health at all sites was good. After 22 years hemlock health had declined to a poor condition and mortality averaged 30%. Differences in health decline were found among the three physiographic mountain regions. Analysis of the variables measured indicated that hemlock stand health decline was positively correlated with the percentage of branches infested with HWA, hemlock diameter at breast height (dbh), and total tree basal area per hectare and negatively correlated with latitude. Crown density, the inverse of Forest Inventory and Analysis (FIA) canopy foliage transparency could be used as a standalone hemlock health measurement.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Detecting early stages of Alzheimer’s disease using a web-based cognitive battery - Jordan R. Hoffmeister; Brady R. Robison; Christopher T. Copeland; Calin I. Prodan; Jim G. Scott; Jordan M. Glenn (GeroScience, 2024)

Identification of novel phytotherapeutic agents for understanding hypertrophic cardiomyopathy via genetic mapping and advanced computational analysis - Abdullahi Tunde Aborode; Onifade Isreal Ayobami; Ammar Usman Danazumi; Christopher Busayo Olowosoke; Haruna Isiyaku Umar; Abraham Osinuga; Aeshah A. Awaji; Fatmah Ali Awaji; Ebenezer Ayomide Omojowolo; Najwa Ahmad Kuthi; Tanveer Shaikh; Babatunde Shuaib Anidu; et al. (Genome Instability & Disease, 2024)

Land subsidence in the Mid-Atlantic United States: Creeping disaster threatens water, energy, and climate security - Christopher A. Scott (Water Security, 2024)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Localized electrocortical activity as a function of single-leg squat phases and its relationship to knee frontal plane stability - Scott Bonnette; Evi Wezenbeek; Jed A. Diekfuss; Taylor Zuleger; Mario Ramirez; Lexie Sengkhammee; Vicente Raja; Gregory D. Myer; Christopher D. Riehm (Experimental Brain Research, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

New approach methodologies to confirm developmental toxicity of pharmaceuticals based on weight of evidence - Natasha R. Catlin; Gregg D. Cappon; Scott D. Davenport; Christine M. Stethem; William S. Nowland; Sarah N. Campion; Christopher J. Bowman (Reproductive Toxicology, 2024)

Changing source waters on the Northeast US Continental Shelf: Variation in nutrient supply and phytoplankton biomass - Kevin D. Friedland; Paula Fratantoni; Adrienne Silver; Damian C. Brady; Avijit Gangopadhyay; Scott I. Large; Ryan E. Morse; David W. Townsend; Marjorie A.M. Friedrichs; D. Christopher Melrose (Continental Shelf Research, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Comparing machine learning and inverse modeling approaches for the source term estimation - Stefano Alessandrini; Scott Meech; Will Cheng; Christopher Rozoff; Rajesh Kumar (Air Quality, Atmosphere & Health, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

Host plant species affect the abundance of spotted wing Drosophila and fruit parasitism across the Allegheny National Forest differentially at variable spatial scales - Daniel P. Roche; Scott H. Stoleson; Christopher T. Rota; William K. Oldland; Christopher M. Lituma (Forest Ecology and Management, 2024)

Biosecurity indemnification and attitudes of United States swine producers towards the prevention of an african swine fever outbreak - Richmond Silvanus Baye; Asim Zia; Scott C. Merrill; Eric M Clark; Christopher Koliba; Julia M. Smith (Preventive Veterinary Medicine, 2024)

Densely populated biofilms and linked iron and sulfur cycles in the fractured-rock continental subsurface - Christopher J. Schuler; Amanda Patsis; Scott C. Alexander; David Hsu; William S. Dowd; Woonghee Lee; Sarick L. Matzen; Matthew A. Marcus; Cody S. Sheik; Jill M. McDermott; Peter K. Kang; Cara M. Santelli; et al. (Geochimica et Cosmochimica Acta, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

New Oldowan locality Sare-Abururu (ca. 1.7 Ma) provides evidence of diverse hominin behaviors on the Homa Peninsula, Kenya - Emma M. Finestone; Thomas W. Plummer; Thomas H. Vincent; Scott A. Blumenthal; Peter W. Ditchfield; Laura C. Bishop; James S. Oliver; Andy I.R. Herries; Christopher Vere Palfery; Timothy P. Lane; Elizabeth McGuire; Jonathan S. Reeves; et al. (Journal of Human Evolution, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Metal accumulation in salt marsh soils along the East Coast of the United States - Kristen E. Jezycki; Elise Rodriguez; Christopher B. Craft; Scott C. Neubauer; James T. Morris; Steven T. Goldsmith; Peleg Kremer; Nathaniel B. Weston (Science of The Total Environment, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

Successful DNA amplification of DNA from non-destructive buccal swabbing in Vespertilionid and Rhinolophid bats - Morgan Hughes; Scott K Brown; Rémi Martin; Christopher H Young; Simon Maddock (Conservation Genetics Resources, 2024)
Acquiring DNA from wild bats (Mammalia: Chiroptera) is typically undertaken utilizing highly invasive (but non-lethal) sampling techniques comprising wing biopsies and occasional blood samples. While non-invasive sampling is possible through the extraction of DNA from faecal samples, it is not always possible to acquire samples from individual bats whilst conducting fieldwork, and as such, this method is primarily applicable to roost occupancy identification. Similarly, wing swabbing is liable to cross-contamination from roost mates. Here we present the first use of oral (buccal) swabbing for successful, species-resolution DNA sequencing of Vespertilionidae and Rhinolophidae in 10 bat species (nine Vespertilionidae and one Rhinolophidae) from the UK.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Understanding visitor attitudes towards the timed-entry reservation system in Rocky Mountain National Park: Contemporary managed access as a social-ecological system - Noah Creany; Christopher A. Monz; Scott M. Esser (Journal of Outdoor Recreation and Tourism, 2024)

Detection of inland water bodies under dense biomass by CYGNSS - Hugo Carreno-Luengo; Christopher S. Ruf; Scott Gleason; Anthony Russel (Remote Sensing of Environment, 2024)

Corticomuscular cross-recurrence analysis reveals between-limb differences in motor control among individuals with ACL reconstruction - Christopher D. Riehm; Scott Bonnette; Justin L. Rush; Jed A. Diekfuss; Moein Koohestani; Gregory D. Myer; Grant E. Norte; David A. Sherman (Experimental Brain Research, 2024)

Perceptions of weather-based pain forecasts and their effect on daily activities - Christopher J. Elcik; Christopher M. Fuhrmann; Scott C. Sheridan; Kathleen Sherman-Morris; Andrew E. Mercer (International Journal of Biometeorology, 2024)

The relationship between greenspace exposure and telomere length in the National Health and Nutrition Examination Survey - S. Scott Ogletree; Jing-Huei Huang; David Reif; Lin Yang; Christopher Dunstan; Nnamdi Osakwe; Jae In Oh; J. Aaron Hipp (Science of The Total Environment, 2023)

Nutrient variability and sediment contribution along a mixed land-use within Sturgeon Creek- Lake Erie watershed - Yu-Ting Chen; Scott O.C. Mundle; Tom Reid; Christopher Weisener (Journal of Environmental Management, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Environment and shipping drive environmental DNA beta‐diversity among commercial ports - Jose Andrés; Paul Czechowski; Erin Grey; Mandana Saebi; Kara Andres; Christopher Brown; Nitesh Chawla; James J. Corbett; Rein Brys; Phillip Cassey; Nancy Correa; Marty R. Deveney; et al. (Molecular Ecology, 2023)
The spread of nonindigenous species by shipping is a large and growing global problem that harms coastal ecosystems and economies and may blur coastal biogeographical patterns. This study coupled eukaryotic environmental DNA (eDNA) metabarcoding with dissimilarity regression to test the hypothesis that ship‐borne species spread homogenizes port communities. We first collected and metabarcoded water samples from ports in Europe, Asia, Australia and the Americas. We then calculated community dissimilarities between port pairs and tested for effects of environmental dissimilarity, biogeographical region and four alternative measures of ship‐borne species transport risk. We predicted that higher shipping between ports would decrease community dissimilarity, that the effect of shipping would be small compared to that of environment dissimilarity and shared biogeography, and that more complex shipping risk metrics (which account for ballast water and stepping‐stone spread) would perform better. Consistent with our hypotheses, community dissimilarities increased significantly with environmental dissimilarity and, to a lesser extent, decreased with ship‐borne species transport risks, particularly if the ports had similar environments and stepping‐stone risks were considered. Unexpectedly, we found no clear effect of shared biogeography, and that risk metrics incorporating estimates of ballast discharge did not offer more explanatory power than simpler traffic‐based risks. Overall, we found that shipping homogenizes eukaryotic communities between ports in predictable ways, which could inform improvements in invasive species policy and management. We demonstrated the usefulness of eDNA metabarcoding and dissimilarity regression for disentangling the drivers of large‐scale biodiversity patterns. We conclude by outlining logistical considerations and recommendations for future studies using this approach.

Emerging human–shark conflicts in the New York Bight: A call for expansive science and management - Oliver N. Shipley; Jill A. Olin; Christopher Scott; Merry Camhi; Michael G. Frisk (Journal of Fish Biology, 2023)
Recent spikes in interactions between humans and sharks in the New York Bight have sparked widespread reporting of possible causalities, many of which lack empirical support. Here we comment on the current state of knowledge regarding shark biology and management in New York waters emphasizing that the possible drivers of increased human–shark interactions are confounded by a lack of historical monitoring data. We outline several key research avenues that should be considered to ensure the safe and sustainable coexistence of humans, sharks, and their prey, in an era of accelerated environmental change.

The paracommons of competition for resource savings: Irrigation water conservation redistributes water between irrigation, nature, and society - Bruce A Lankford; Christopher A Scott (Resources, Conservation and Recycling, 2023)

Predicting the fine‐scale spatial distribution of zoonotic reservoirs using computer vision - Nathan C. Layman; Andrew J. Basinski; Boyu Zhang; Evan A. Eskew; Brian H. Bird; Bruno M. Ghersi; James Bangura; Elisabeth Fichet‐Calvet; Christopher H. Remien; Mohamed Vandi; Mohamed Bah; Scott L. Nuismer (Ecology Letters, 2023)
Zoonotic diseases threaten human health worldwide and are often associated with anthropogenic disturbance. Predicting how disturbance influences spillover risk is critical for effective disease intervention but difficult to achieve at fine spatial scales. Here, we develop a method that learns the spatial distribution of a reservoir species from aerial imagery. Our approach uses neural networks to extract features of known or hypothesized importance from images. The spatial distribution of these features is then summarized and linked to spatially explicit reservoir presence/absence data using boosted regression trees. We demonstrate the utility of our method by applying it to the reservoir of Lassa virus, Mastomys natalensis , within the West African nations of Sierra Leone and Guinea. We show that, when trained using reservoir trapping data and publicly available aerial imagery, our framework learns relationships between environmental features and reservoir occurrence and accurately ranks areas according to the likelihood of reservoir presence.

Bio-physical determinants of sediment accumulation on an offshore coral reef: A snapshot study - Sterling B. Tebbett; Jodie A. Schlaefer; Casey L. Bowden; William P. Collins; Christopher R. Hemingson; Scott D. Ling; Juliano Morais; Renato A. Morais; Alexandre C. Siqueira; Robert P. Streit; Sam Swan; David R. Bellwood (Science of The Total Environment, 2023)

Sustainability of bioenergy – Mapping the risks & benefits to inform future bioenergy systems - Andrew James Welfle; Alberto Almena; Muhammad Naveed Arshad; Scott William Banks; Isabela Butnar; Katie Jane Chong; SamuelJ.G. Cooper; Helen Daly; Samira Garcia Freites; Fatih Güleç; Christopher Hardacre; Robert Holland; et al. (Biomass and Bioenergy, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

A general approach for evaluating of the coverage, resolution, and representation of streamflow monitoring networks - Christopher P. Konrad; Scott W. Anderson (Environmental Monitoring and Assessment, 2023)
Streamflow monitoring networks provide information for a wide range of public interests in river and streams. A general approach to evaluate monitoring for different interests is developed to support network planning and design. The approach defines three theoretically distinct information metrics (coverage, resolution, and representation) based on the spatial distribution of a variable of interest. Coverage is the fraction of information that a network can provide about a variable when some areas are not monitored. Resolution is the information available from the network relative to the maximum information possible given the number of sites in the network. Representation is the information that a network provides about a benchmark distribution of a variable. Information is defined using Shannon entropy where the spatial discretization of a variable among spatial elements of a landscape or sites in a network indicates the uncertainty in the spatial distribution of the variable. This approach supports the design of networks for monitoring of variables with heterogeneous spatial distributions (“hot spots” and patches) that might otherwise be unmonitored because they occupy insignificant portions of the landscape. Areas where monitoring will maintain or improve the metrics serve as objective priorities for public interests in network design. The approach is demonstrated for the streamflow monitoring network operated by the United States Geological Survey during water year 2020 indicating gaps in the coverage of coastal rivers and the resolution of low flows.

A marine protected area network does not confer community structure resilience to a marine heatwave across coastal ecosystems - Joshua G. Smith; Christopher M. Free; Cori Lopazanski; Julien Brun; Clarissa R. Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; Scott L. Hamilton; David Mouillot; et al. (Global Change Biology, 2023)
Marine protected areas (MPAs) have gained attention as a conservation tool for enhancing ecosystem resilience to climate change. However, empirical evidence explicitly linking MPAs to enhanced ecological resilience is limited and mixed. To better understand whether MPAs can buffer climate impacts, we tested the resistance and recovery of marine communities to the 2014–2016 Northeast Pacific heatwave in the largest scientifically designed MPA network in the world off the coast of California, United States. The network consists of 124 MPAs (48 no‐take state marine reserves, and 76 partial‐take or special regulation conservation areas) implemented at different times, with full implementation completed in 2012. We compared fish, benthic invertebrate, and macroalgal community structure inside and outside of 13 no‐take MPAs across rocky intertidal, kelp forest, shallow reef, and deep reef nearshore habitats in California's Central Coast region from 2007 to 2020. We also explored whether MPA features, including age, size, depth, proportion rock, historic fishing pressure, habitat diversity and richness, connectivity, and fish biomass response ratios (proxy for ecological performance), conferred climate resilience for kelp forest and rocky intertidal habitats spanning 28 MPAs across the full network. Ecological communities dramatically shifted due to the marine heatwave across all four nearshore habitats, and MPAs did not facilitate habitat‐wide resistance or recovery. Only in protected rocky intertidal habitats did community structure significantly resist marine heatwave impacts. Community shifts were associated with a pronounced decline in the relative proportion of cold water species and an increase in warm water species. MPA features did not explain resistance or recovery to the marine heatwave. Collectively, our findings suggest that MPAs have limited ability to mitigate the impacts of marine heatwaves on community structure. Given that mechanisms of resilience to climate perturbations are complex, there is a clear need to expand assessments of ecosystem‐wide consequences resulting from acute climate‐driven perturbations, and the potential role of regulatory protection in mitigating community structure changes.

Structural and species diversity explain aboveground carbon storage in forests across the United States: Evidence from GEDI and forest inventory data - Erin T.H. Crockett; Jeff W. Atkins; Qinfeng Guo; Ge Sun; Kevin M. Potter; Scott Ollinger; Carlos A. Silva; Hao Tang; Christopher W. Woodall; Justin Holgerson; Jingfeng Xiao (Remote Sensing of Environment, 2023)

Particulate matter, traffic-related air pollutants, and circulating C-reactive protein levels: The Multiethnic Cohort Study - Meera Sangaramoorthy; Juan Yang; Chiuchen Tseng; Jun Wu; Beate Ritz; Timothy V. Larson; Scott Fruin; Daniel O. Stram; Sung-shim Lani Park; Adrian A. Franke; Lynne R. Wilkens; Jonathan M. Samet; et al. (Environmental Pollution, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Riparian and terrestrial grasses display unexpected tolerance to cool-season inundation - Vanja Kitanović; Joe Greet; Scott A. McKendrick; Christopher S. Jones (Wetlands Ecology and Management, 2023)
Vegetation condition has declined along many regulated river systems globally due to alteration of flow regimes via flow regulation. Understanding how plants respond to inundation is critical for managing regulated river flows to improve riparian vegetation condition. We experimentally tested the effects of inundation duration on the survival and growth of six tufted grass species commonly found in riparian zones in south-eastern Australia. We conducted three nursery-based experiments in late winter/early spring, corresponding with natural temperate flow peaks and managed flows, with inundation treatments on: (1) established plants, up to 35 days inundation; (2) seedlings, up to 25 days inundation; and (3) established plants, up to 53 days inundation including additional shaded treatments. Plant survival, height and biomass growth, and onset of flowering were recorded for established plants, and, for seedlings, survival only. Plant height and biomass growth declined with longer inundation duration across all species, although surprisingly few established plants died. Unexpectedly, grass seedlings were generally tolerant of inundation also, although there was some evidence of increased mortality for the longest treatment (25 days inundation). Shading did not result in increased mortality or reduced height growth of inundated plants. Inundation effects on the onset of flowering were modest and varied between species ranging from earlier to delayed onset. Our results suggest that tufted grasses are tolerant of cool-season inundation. Given that mortality of these species has been observed in the field and experimentally under shorter inundation periods in warmer conditions (late spring and summer), we suggest that seasonal timing of inundation is critical in determining plant responses to inundation.

MortCam: An Artificial Intelligence-aided fish mortality detection and alert system for recirculating aquaculture - Rakesh Ranjan; Kata Sharrer; Scott Tsukuda; Christopher Good (Aquacultural Engineering, 2023)

Evapotranspiration regulates leaf temperature and respiration in dryland vegetation - Christopher L. Kibler; Anna T. Trugman; Dar A. Roberts; Christopher J. Still; Russell L. Scott; Kelly K. Caylor; John C. Stella; Michael Bliss Singer (Agricultural and Forest Meteorology, 2023)

Fruit parasitism and abundance of a non-native insect pest affects abundances of some songbirds - Daniel P. Roche; Scott H. Stoleson; Christopher T. Rota; William K. Oldland; Christopher M. Lituma (Biological Invasions, 2023)

Scratching the surface? A histotaphonomic study of human remains at Neolithic Çatalhöyük - Scott D. Haddow; Camilla Mazzucato; Sıla Mangaloğlu-Votruba; Barış Yağcı; Thomas Booth; Eline M. J. Schotsmans; Christopher J. Knüsel (Archaeological and Anthropological Sciences, 2023)

Drivers of fishery status for the cultural keystone pāua (Haliotis iris) in Customary fishery Protection Areas in Aotearoa New Zealand - Finn J. Ryder; Gaya Gnanalingam; Daniel W. Pritchard; William J. Rayment; Nigel J. Scott; Christopher D. Hepburn (Fisheries Research, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Targeting Redundant ROBO1 and SDF-1 Pathways Prevents Adult Hemangioblast Derived-EPC and CEC Activity Effectively Blocking Tumor Neovascularization - Anitha K. Shenoy; Liya Pi; Alexander P. Ligocki; Koji Hosaka; Christopher R. Cogle; Edward W. Scott (Stem Cell Reviews and Reports, 2023)

The transcription regulator ATF4 is a mediator of skeletal muscle aging - Matthew J. Miller; George R. Marcotte; Nathan Basisty; Cameron Wehrfritz; Zachary C. Ryan; Matthew D. Strub; Andrew T. McKeen; Jennifer I. Stern; Karl A. Nath; Blake B. Rasmussen; Andrew R. Judge; Birgit Schilling; et al. (GeroScience, 2023)
Aging slowly erodes skeletal muscle strength and mass, eventually leading to profound functional deficits and muscle atrophy. The molecular mechanisms of skeletal muscle aging are not well understood. To better understand mechanisms of muscle aging, we investigated the potential role of ATF4, a transcription regulatory protein that can rapidly promote skeletal muscle atrophy in young animals deprived of adequate nutrition or activity. To test the hypothesis that ATF4 may be involved in skeletal muscle aging, we studied fed and active muscle-specific ATF4 knockout mice (ATF4 mKO mice) at 6 months of age, when wild-type mice have achieved peak muscle mass and function, and at 22 months of age, when wild-type mice have begun to manifest age-related muscle atrophy and weakness. We found that 6-month-old ATF4 mKO mice develop normally and are phenotypically indistinguishable from 6-month-old littermate control mice. However, as ATF4 mKO mice become older, they exhibit significant protection from age-related declines in strength, muscle quality, exercise capacity, and muscle mass. Furthermore, ATF4 mKO muscles are protected from some of the transcriptional changes characteristic of normal muscle aging (repression of certain anabolic mRNAs and induction of certain senescence-associated mRNAs), and ATF4 mKO muscles exhibit altered turnover of several proteins with important roles in skeletal muscle structure and metabolism. Collectively, these data suggest ATF4 as an essential mediator of skeletal muscle aging and provide new insight into a degenerative process that impairs the health and quality of life of many older adults.

Highly socially vulnerable communities exhibit disproportionately increased viral loads as measured in community wastewater - William M. Baldwin; Robert D. Dayton; Aaron W. Bivins; Rona S. Scott; Andrew D. Yurochko; John A. Vanchiere; Terry Davis; Connie L. Arnold; Jose.E.T. Asuncion; Mohammad A.N. Bhuiyan; Brandon Snead; William Daniel; et al. (Environmental Research, 2023)

To burn or not to burn: An empirical assessment of the impacts of wildfires and prescribed fires on trace element concentrations in Western US streams - Mussie T. Beyene; Scott G. Leibowitz; Christopher J. Dunn; Kevin D. Bladon (Science of The Total Environment, 2023)

Atmospheric humidity and temperature sounding from the CubeSat TROPICS mission: Early performance evaluation with MiRS - John Xun Yang; Yong-Keun Lee; Christopher Grassotti; Kevin Garrett; Quanhua Liu; William Blackwell; R. Vincent Leslie; Tom Greenwald; Ralf Bennartz; Scott Braun (Remote Sensing of Environment, 2023)

Biofilm inspired fabrication of functional bacterial cellulose through ex-situ and in-situ approaches - Katie A. Gilmour; Mahab Aljannat; Christopher Markwell; Paul James; Jane Scott; Yunhong Jiang; Hamdi Torun; Martyn Dade-Robertson; Meng Zhang (Carbohydrate Polymers, 2023)

Effects of image data quality on a convolutional neural network trained in-tank fish detection model for recirculating aquaculture systems - Rakesh Ranjan; Kata Sharrer; Scott Tsukuda; Christopher Good (Computers and Electronics in Agriculture, 2023)

Estimates of broadband upwelling irradiance from GOES-16 ABI - Kevin McCloskey; Sixing Chen; Vincent R. Meijer; Joe Yue-Hei Ng; Geoff Davis; Carl Elkin; Christopher Van Arsdale; Scott Geraedts (Remote Sensing of Environment, 2023)

Development and Evaluation of High-Density SNP Arrays for the Eastern Oyster Crassostrea virginica - Ximing Guo; Jonathan B. Puritz; Zhenwei Wang; Dina Proestou; Standish Allen; Jessica Small; Klara Verbyla; Honggang Zhao; Jaime Haggard; Noah Chriss; Dan Zeng; Kathryn Lundgren; et al. (Marine Biotechnology, 2023)

High polygenic risk score for exceptional longevity is associated with a healthy metabolic profile - Mary Revelas; Anbupalam Thalamuthu; Anna Zettergren; Christopher Oldmeadow; Jenna Najar; Nazib M. Seidu; Nicola J. Armstrong; Carlos Riveros; John B. Kwok; Peter R. Schofield; Julian N. Trollor; Margda Waern; et al. (GeroScience, 2023)
Healthy metabolic measures in humans are associated with longevity. Dysregulation leads to metabolic syndrome (MetS) and negative health outcomes. Recent exceptional longevity (EL) genome wide association studies have facilitated estimation of an individual’s polygenic risk score (PRS) for EL. We tested the hypothesis that individuals with high ELPRS have a low prevalence of MetS. Participants were from five cohorts of middle-aged to older adults. The primary analyses were performed in the UK Biobank (UKBB) ( n = 407,800, 40–69 years). Replication analyses were undertaken using three Australian studies: Hunter Community Study ( n = 2122, 55–85 years), Older Australian Twins Study ( n = 539, 65–90 years) and Sydney Memory and Ageing Study ( n = 925, 70–90 years), as well as the Swedish Gothenburg H70 Birth Cohort Studies ( n = 2273, 70–93 years). MetS was defined using established criteria. Regressions and meta-analyses were performed with the ELPRS and MetS and its components. Generally, MetS prevalence (22–30%) was higher in the older cohorts. In the UKBB, high EL polygenic risk was associated with lower MetS prevalence (OR = 0.94, p = 1.84 × 10 –42 ) and its components ( p < 2.30 × 10 – 8 ). Meta-analyses of the replication cohorts showed nominal associations with MetS ( p = 0.028) and 3 MetS components ( p < 0.05). This work suggests individuals with a high polygenic risk for EL have a healthy metabolic profile promoting longevity.

Stronger fertilization effects on aboveground versus belowground plant properties across nine U.S. grasslands - Adrienne B. Keller; Christopher A. Walter; Dana M. Blumenthal; Elizabeth T. Borer; Scott L. Collins; Lang C. DeLancey; Philip A. Fay; Kirsten S. Hofmockel; Johannes M. H. Knops; Andrew D. B. Leakey; Melanie A. Mayes; Eric W. Seabloom; et al. (Ecology, 2023)
Increased nutrient inputs due to anthropogenic activity are expected to increase primary productivity across terrestrial ecosystems, but changes in allocation aboveground versus belowground with nutrient addition have different implications for soil carbon (C) storage. Thus, given that roots are major contributors to soil C storage, understanding belowground net primary productivity (BNPP) and biomass responses to changes in nutrient availability is essential to predicting carbon–climate feedbacks in the context of interacting global environmental changes. To address this knowledge gap, we tested whether a decade of nitrogen (N) and phosphorus (P) fertilization consistently influenced aboveground and belowground biomass and productivity at nine grassland sites spanning a wide range of climatic and edaphic conditions in the continental United States. Fertilization effects were strong aboveground, with both N and P addition stimulating aboveground biomass at nearly all sites (by 30% and 36%, respectively, on average). P addition consistently increased root production (by 15% on average), whereas other belowground responses to fertilization were more variable, ranging from positive to negative across sites. Site‐specific responses to P were not predicted by the measured covariates. Atmospheric N deposition mediated the effect of N fertilization on root biomass and turnover. Specifically, atmospheric N deposition was positively correlated with root turnover rates, and this relationship was amplified with N addition. Nitrogen addition increased root biomass at sites with low N deposition but decreased it at sites with high N deposition. Overall, these results suggest that the effects of nutrient supply on belowground plant properties are context dependent, particularly with regard to background N supply rates, demonstrating that site conditions must be considered when predicting how grassland ecosystems will respond to increased nutrient loading from anthropogenic activity.

Comparison of two turbulence parameterisations for the simulation of the concentration variance dispersion - Enrico Ferrero; Stefano Alessandrini; Scott Meech; Christopher Rozoff; Dietmar Oettl (Air Quality, Atmosphere & Health, 2023)
In this work, we compare two different parameterisations for the wind velocity–component standard deviations. The first one is the (Hanna 1982) parameterisation, while the second is the (Scire et al. 2000) parameterisation, which provide the proper values and vertical structure for the wind standard deviations in the convective, neutral and stable layers, needed as input the Lagrangian stochastic model SPRAYWEB. The results of the model simulations carried out using the two parameterisations are compared, in terms of both mean concentration and concentration standard deviation, by evaluating some statistical indexes and trough scatter- and qq-plots.

Technology Transfer of PMEL Tsunami Research Protects Populations and Expands the New Blue Economy - Vasily Titov; Christian Meinig; Scott Stalin; Yong Wei; Christopher Moore; Eddie Bernard (Oceanography, 2023)
NOAA Pacific Marine Environmental Laboratory’s (PMEL’s) approach to tsunami research is unique among such laboratories in that tsunami observations and modeling are under one roof, offering the advantages of enhancing the speed and lowering the cost of developments. Here, we chronicle the history of the transfer of deep-ocean observational and flooding modeling technologies within and outside of NOAA and provide a case study for future transfers. PMEL and partners’ efforts in transferring tsunami technology have been very successful, resulting in improved protection of global communities with high tsunami risk while enhancing the new blue economy. The transfer of observational technology within NOAA required years of effort, while the transfer outside of NOAA only required a patent and license agreement. During the transfer process, three additional generations of observational technologies were created. The transfer of tsunami flooding modeling technology required a validation process for transfer into NOAA operations and an international training program to allow access to the technology by other countries. During this model development, a web-based product was created to simplify the use of and access to these models for both real-time and hazard assessment applications. We present lessons learned from these transfers, including the need for support as long as the technology is in use. The tsunami transfer process created a wealth of economic expansion while protecting coastal citizens from future tsunamis.

Two canonically aerobic foraminifera express distinct peroxisomal and mitochondrial metabolisms - Christopher Powers; Fatma Gomaa; Elizabeth B. Billings; Daniel R. Utter; David J. Beaudoin; Virginia P. Edgcomb; Colleen M. Hansel; Scott D. Wankel; Helena L. Filipsson; Ying Zhang; Joan M. Bernhard (Frontiers in Marine Science, 2022)
Certain benthic foraminifera thrive in marine sediments with low or undetectable oxygen. Potential survival avenues used by these supposedly aerobic protists include fermentation and anaerobic respiration, although details on their adaptive mechanisms remain elusive. To better understand the metabolic versatility of foraminifera, we studied two benthic species that thrive in oxygen-depleted marine sediments. Here we detail, via transcriptomics and metatranscriptomics, differential gene expression of Nonionella stella and Bolivina argentea , collected from Santa Barbara Basin, California, USA, in response to varied oxygenation and chemical amendments. Organelle-specific metabolic reconstructions revealed these two species utilize adaptable mitochondrial and peroxisomal metabolism. N. stella , most abundant in anoxia and characterized by lack of food vacuoles and abundance of intracellular lipid droplets, was predicted to couple the putative peroxisomal beta-oxidation and glyoxylate cycle with a versatile electron transport system and a partial TCA cycle. In contrast, B. argentea , most abundant in hypoxia and contains food vacuoles, was predicted to utilize the putative peroxisomal gluconeogenesis and a full TCA cycle but lacks the expression of key beta-oxidation and glyoxylate cycle genes. These metabolic adaptations likely confer ecological success while encountering deoxygenation and expand our understanding of metabolic modifications and interactions between mitochondria and peroxisomes in protists.

A 3D Lagrangian stochastic particle model for the concentration variance dispersion - Enrico Ferrero; Stefano Alessandrini; Scott Meech; Christopher Rozoff (Bulletin of Atmospheric Science and Technology, 2022)
A new scheme for the concentration variance calculation is assessed using field experiment data. The scheme is introduced in a Lagrangian stochastic particle model. The model provides run-time mean concentrations and concentrations’ variance 3D fields; thus, it does not need any off-line post-processing. The model is tested against the FFT-07 field experiment which involves a series of tracer releases. It is a short-range (500 m) highly instrumented experiment. In this work, measurement of tracer concentrations, emitted from a ground level point source is used to assess the ability of the new model in predicting the mean concentration, concentration variance, and the concentration fluctuation intensity at the ground level with a high spatial resolution. The results of the intercomparison are shown and discussed in terms of statistical plots and indices.

A science-based policy for managing free-roaming cats - Christopher A. Lepczyk; David C. Duffy; David M. Bird; Michael Calver; Dmitry Cherkassky; Linda Cherkassky; Christopher R. Dickman; David Hunter; David Jessup; Travis Longcore; Scott R. Loss; Kerrie Anne T. Loyd; et al. (Biological Invasions, 2022)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Environmental DNA Methods for Ecological Monitoring and Biodiversity Assessment in Estuaries - Raman P. Nagarajan; Mallory Bedwell; Ann E. Holmes; Thiago Sanches; Shawn Acuña; Melinda Baerwald; Matthew A. Barnes; Scott Blankenship; Richard E. Connon; Kristy Deiner; Daphne Gille; Caren S. Goldberg; et al. (Estuaries and Coasts, 2022)
Environmental DNA (eDNA) detection methods can complement traditional biomonitoring to yield new ecological insights in aquatic systems. However, the conceptual and methodological frameworks for aquatic eDNA detection and interpretation were developed primarily in freshwater environments and have not been well established for estuaries and marine environments that are by nature dynamic, turbid, and hydrologically complex. Environmental context and species life history are critical for successful application of eDNA methods, and the challenges associated with eDNA detection in estuaries were the subject of a symposium held at the University of California Davis on January 29, 2020 ( https://marinescience.ucdavis.edu/engagement/past-events/edna ). Here, we elaborate upon topics addressed in the symposium to evaluate eDNA methods in the context of monitoring and biodiversity studies in estuaries. We first provide a concise overview of eDNA science and methods, and then examine the San Francisco Estuary (SFE) as a case study to illustrate how eDNA detection can complement traditional monitoring programs and provide regional guidance on future potential eDNA applications. Additionally, we offer recommendations for enhancing communication between eDNA scientists and natural resource managers, which is essential for integrating eDNA methods into existing monitoring programs. Our intent is to create a resource that is accessible to those outside the field of eDNA, especially managers, without oversimplifying the challenges or advantages of these methods.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Testing inter-observer error under a collaborative research framework for studying lithic shape variability - Lucy Timbrell; Christopher Scott; Behailu Habte; Yosef Tefera; Hélène Monod; Mouna Qazzih; Benjamin Marais; Wendy Black; Christine Maroma; Emmanuel Ndiema; Struan Henderson; Katherine Elmes; et al. (Archaeological and Anthropological Sciences, 2022)
Evaluating error that arises through the aggregation of data recorded by multiple observers is a key consideration in many metric and geometric morphometric analyses of stone tool shape. One of the most common approaches involves the convergence of observers for repeat trails on the same set of artefacts: however, this is logistically and financially challenging when collaborating internationally and/or at a large scale. We present and evaluate a unique alternative for testing inter-observer error, involving the development of 3D printed copies of a lithic reference collection for distribution among observers. With the aim of reducing error, clear protocols were developed for photographing and measuring the replicas, and inter-observer variability was assessed on the replicas in comparison with a corresponding data set recorded by a single observer. Our results demonstrate that, when the photography procedure is standardized and dimensions are clearly defined, the resulting metric and geometric morphometric data are minimally affected by inter-observer error, supporting this method as an effective solution for assessing error under collaborative research frameworks. Collaboration is becoming increasingly important within archaeological and anthropological sciences in order to increase the accessibility of samples, encourage dual-project development between foreign and local researchers and reduce the carbon footprint of collection-based research. This study offers a promising validation of a collaborative research design whereby researchers remotely work together to produce comparable data capturing lithic shape variability.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem - Michaela Plein; Katherine R. O'Brien; Matthew H. Holden; Matthew P. Adams; Christopher M. Baker; Nigel G. Bean; Scott A. Sisson; Michael Bode; Kerrie L. Mengersen; Eve McDonald‐Madden (Conservation Biology, 2022)
Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation.

Webinar and survey on quality management principles within the Australian and New Zealand ACPSEM Workforce - Emily Simpson-Page; Paul Coogan; Tomas Kron; Nicholas Lowther; Rebecca Murray; Christopher Noble; Ian Smith; Rachael Wilks; Scott B. Crowe (Physical and Engineering Sciences in Medicine, 2022)

Echofilter: A Deep Learning Segmention Model Improves the Automation, Standardization, and Timeliness for Post-Processing Echosounder Data in Tidal Energy Streams - Scott C. Lowe; Louise P. McGarry; Jessica Douglas; Jason Newport; Sageev Oore; Christopher Whidden; Daniel J. Hasselman (Frontiers in Marine Science, 2022)
Understanding the abundance and distribution of fish in tidal energy streams is important for assessing the risks presented by the introduction of tidal energy devices into the habitat. However, tidal current flows suitable for tidal energy development are often highly turbulent and entrain air into the water, complicating the interpretation of echosounder data. The portion of the water column contaminated by returns from entrained air must be excluded from data used for biological analyses. Application of a single algorithm to identify the depth-of-penetration of entrained air is insufficient for a boundary that is discontinuous, depth-dynamic, porous, and varies with tidal flow speed. Using a case study at a tidal energy demonstration site in the Bay of Fundy, we describe the development and application of deep machine learning models with a U-Net based architecture that produce a pronounced and substantial improvement in the automated detection of the extent to which entrained air has penetrated the water column. Our model, Echofilter, was found to be highly responsive to the dynamic range of turbulence conditions and sensitive to the fine-scale nuances in the boundary position, producing an entrained-air boundary line with an average error of 0.33 m on mobile downfacing and 0.5–1.0 m on stationary upfacing data, less than half that of existing algorithmic solutions. The model’s overall annotations had a high level of agreement with the human segmentation, with an intersection-over-union score of 99% for mobile downfacing recordings and 92–95% for stationary upfacing recordings. This resulted in a 50% reduction in the time required for manual edits when compared to the time required to manually edit the line placement produced by the currently available algorithms. Because of the improved initial automated placement, the implementation of the models permits an increase in the standardization and repeatability of line placement.

Urban biodiversity: State of the science and future directions - Christine C. Rega-Brodsky; Myla F. J. Aronson; Max R. Piana; Ela-Sita Carpenter; Amy K. Hahs; Adriana Herrera-Montes; Sonja Knapp; D. Johan Kotze; Christopher A. Lepczyk; Marco Moretti; Allyson B. Salisbury; Nicholas S. G. Williams; et al. (Urban Ecosystems, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Unbound Brain-to-Plasma Partition Coefficient, Kp,uu,brain—a Game Changing Parameter for CNS Drug Discovery and Development - Irena Loryan; Andreas Reichel; Bo Feng; Christoffer Bundgaard; Christopher Shaffer; Cory Kalvass; Dallas Bednarczyk; Denise Morrison; Dominique Lesuisse; Edmund Hoppe; Georg C. Terstappen; Holger Fischer; et al. (Pharmaceutical Research, 2022)
Purpose More than 15 years have passed since the first description of the unbound brain-to-plasma partition coefficient (K p,uu,brain ) by Prof. Margareta Hammarlund-Udenaes, which was enabled by advancements in experimental methodologies including cerebral microdialysis. Since then, growing knowledge and data continue to support the notion that the unbound (free) concentration of a drug at the site of action, such as the brain, is the driving force for pharmacological responses. Towards this end, K p,uu,brain is the key parameter to obtain unbound brain concentrations from unbound plasma concentrations. Methods To understand the importance and impact of the K p,uu,brain concept in contemporary drug discovery and development, a survey has been conducted amongst major pharmaceutical companies based in Europe and the USA. Here, we present the results from this survey which consisted of 47 questions addressing: 1) Background information of the companies, 2) Implementation, 3) Application areas, 4) Methodology, 5) Impact and 6) Future perspectives. Results and conclusions From the responses, it is clear that the majority of the companies (93%) has established a common understanding across disciplines of the concept and utility of K p,uu,brain as compared to other parameters related to brain exposure. Adoption of the K p,uu,brain concept has been mainly driven by individual scientists advocating its application in the various companies rather than by a top-down approach. Remarkably, 79% of all responders describe the portfolio impact of K p,uu,brain implementation in their companies as ‘game-changing’. Although most companies (74%) consider the current toolbox for K p,uu,brain assessment and its validation satisfactory for drug discovery and early development, areas of improvement and future research to better understand human brain pharmacokinetics/pharmacodynamics translation have been identified.

Global Synthesis of Air-Sea CO2 Transfer Velocity Estimates From Ship-Based Eddy Covariance Measurements - Mingxi Yang; Thomas G. Bell; Jean-Raymond Bidlot; Byron W. Blomquist; Brian J. Butterworth; Yuanxu Dong; Christopher W. Fairall; Sebastian Landwehr; Christa A. Marandino; Scott D. Miller; Eric S. Saltzman; Alexander Zavarsky (Frontiers in Marine Science, 2022)
The air-sea gas transfer velocity ( K 660 ) is typically assessed as a function of the 10-m neutral wind speed ( U 10n ), but there remains substantial uncertainty in this relationship. Here K 660 of CO 2 derived with the eddy covariance (EC) technique from eight datasets (11 research cruises) are reevaluated with consistent consideration of solubility and Schmidt number and inclusion of the ocean cool skin effect. K 660 shows an approximately linear dependence with the friction velocity ( u * ) in moderate winds, with an overall relative standard deviation (relative standard error) of about 20% (7%). The largest relative uncertainty in K 660 occurs at low wind speeds, while the largest absolute uncertainty in K 660 occurs at high wind speeds. There is an apparent regional variation in the steepness of the K 660 - u * relationships: North Atlantic ≥ Southern Ocean > other regions (Arctic, Tropics). Accounting for sea state helps to collapse some of this regional variability in K 660 using the wave Reynolds number in very large seas and the mean squared slope of the waves in small to moderate seas. The grand average of EC-derived K 660 ( − 1.47 + 76.67 u * + 20.48 u * 2 o r 0.36 + 1.203 U 10 n + 0.167 U 10 n 2 ) is similar at moderate to high winds to widely used dual tracer-based K 660 parametrization, but consistently exceeds the dual tracer estimate in low winds, possibly in part due to the chemical enhancement in air-sea CO 2 exchange. Combining the grand average of EC-derived K 660 with the global distribution of wind speed yields a global average transfer velocity that is comparable with the global radiocarbon ( 14 C) disequilibrium, but is ~20% higher than what is implied by dual tracer parametrizations. This analysis suggests that CO 2 fluxes computed using a U 10 n 2 dependence with zero intercept (e.g., dual tracer) are likely underestimated at relatively low wind speeds.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

SGLT2 inhibition attenuates arterial dysfunction and decreases vascular F-actin content and expression of proteins associated with oxidative stress in aged mice - Rogerio N. Soares; Francisco I. Ramirez-Perez; Francisco J. Cabral-Amador; Mariana Morales-Quinones; Christopher A. Foote; Thaysa Ghiarone; Neekun Sharma; Gavin Power; James A. Smith; R. Scott Rector; Luis A. Martinez-Lemus; Jaume Padilla; et al. (GeroScience, 2022)
Aging of the vasculature is characterized by endothelial dysfunction and arterial stiffening, two key events in the pathogenesis of cardiovascular disease (CVD). Treatment with sodium glucose transporter 2 (SGLT2) inhibitors is now known to decrease cardiovascular morbidity and mortality in type 2 diabetes. However, whether SGLT2 inhibition attenuates vascular aging is unknown. We first confirmed in a cohort of adult subjects that aging is associated with impaired endothelial function and increased arterial stiffness and that these two variables are inversely correlated. Next, we investigated whether SGLT2 inhibition with empagliflozin (Empa) ameliorates endothelial dysfunction and reduces arterial stiffness in aged mice with confirmed vascular dysfunction. Specifically, we assessed mesenteric artery endothelial function and stiffness (via flow-mediated dilation and pressure myography mechanical responses, respectively) and aortic stiffness (in vivo via pulse wave velocity and ex vivo via atomic force microscopy) in Empa-treated (14 mg/kg/day for 6 weeks) and control 80-week-old C57BL/6 J male mice. We report that Empa-treated mice exhibited improved mesenteric endothelial function compared with control, in parallel with reduced mesenteric artery and aortic stiffness. Additionally, Empa-treated mice had greater vascular endothelial nitric oxide synthase activation, lower phosphorylated cofilin, and filamentous actin content, with downregulation of pathways involved in production of reactive oxygen species. Our findings demonstrate that Empa improves endothelial function and reduces arterial stiffness in a preclinical model of aging, making SGLT2 inhibition a potential therapeutic alternative to reduce the progression of CVD in older individuals. Graphical abstract

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Perceptions of and barriers to cancer screening by the sexual and gender minority community: a glimpse into the health care disparity - Joseph Lombardo; Kevin Ko; Ayako Shimada; Nicolas Nelson; Christopher Wright; Jerry Chen; Alisha Maity; Marissa L. Ruggiero; Scott Richard; Dimitrios Papanagnou; Edith Mitchell; Amy Leader; et al. (Cancer Causes & Control, 2022)

Oceans and society: feedbacks between ocean and human health - Kirsty L. Nash; Ingrid van Putten; Karen A. Alexander; Silvana Bettiol; Christopher Cvitanovic; Anna K. Farmery; Emily J. Flies; Sierra Ison; Rachel Kelly; Mary Mackay; Linda Murray; Kimberley Norris; et al. (Reviews in Fish Biology and Fisheries, 2022)

Connecting to the oceans: supporting ocean literacy and public engagement - Rachel Kelly; Karen Evans; Karen Alexander; Silvana Bettiol; Stuart Corney; Coco Cullen-Knox; Christopher Cvitanovic; Kristy de Salas; Gholam Reza Emad; Liam Fullbrook; Carolina Garcia; Sierra Ison; et al. (Reviews in Fish Biology and Fisheries, 2022)

Geographical variability in the relationship between synoptic weather type and emergency department visits for pain across North Carolina - Christopher Elcik; Christopher M. Fuhrmann; Scott C. Sheridan; Andrew E. Mercer; Kathleen Sherman-Morris (International Journal of Biometeorology, 2022)

Caffeine and attentional control: improved and impaired performance in healthy older adults and Parkinson’s disease according to task demands - Kanch Sharma; Sean James Fallon; Thomas Davis; Scott Ankrett; Greg Munro; Gary Christopher; Elizabeth Coulthard (Psychopharmacology, 2022)
Introduction Caffeine is frequently consumed to boost goal-directed attention. These procognitive effects may occur due to the adenosine-mediated enhancement of monoamines, such as dopamine, after caffeine administration. As such, caffeine’s beneficial effects may be altered in conditions such as Parkinson’s disease (PD). However, whether caffeine improves cognition, and at what cost, has not been experimentally established in patients with neurodegenerative disease. Methods Single-dose trials to probe cognitive effects of caffeine are often confounded by short-term caffeine abstinence which conflates caffeine’s effects with treatment of withdrawal. Using a placebo controlled, blinded, randomised trial design, we assessed the effect of 100 mg of caffeine across well-established tasks (Choice reaction time, Stroop Task and Rapid Serial Visual Presentation Task; RSVP) that probe different aspects of attention in PD patients ( n = 24) and controls ( n = 44). Critically, participants withdrew from caffeine for a week prior to testing to eliminate the possibility that withdrawal reversal explained any cognitive benefit. Results Caffeine administration was found to reduce the overall number of errors in patients and controls on the Stroop ( p = .018, η 2 p = .086) and Choice reaction time ( p < . 0001, η 2 p = .588) tasks, but there was no specific effect of caffeine on ignoring irrelevant information in the Stroop task. On the RSVP task, caffeine improved dual item accuracy ( p = .037) but impaired single item accuracy ( p = .044). Across all tasks, there was little evidence that caffeine has different effects in PD participants and controls. Conclusion When removing withdrawal effects as a factor, we demonstrate caffeine has beneficial effects on selective attention but is a double-edge sword for visual temporal attention and would need careful targeting to be clinically useful.

Soil carbon stocks in temperate grasslands differ strongly across sites but are insensitive to decade‐long fertilization - Adrienne B. Keller; Elizabeth T. Borer; Scott L. Collins; Lang C. DeLancey; Philip A. Fay; Kirsten S. Hofmockel; Andrew D.B. Leakey; Melanie A. Mayes; Eric W. Seabloom; Christopher A. Walter; Yong Wang; Qian Zhao; et al. (Global Change Biology, 2022)
Enhancing soil carbon (C) storage has the potential to offset human‐caused increases in atmospheric CO 2 . Rising CO 2 has occurred concurrently with increasing supply rates of biologically limiting nutrients such as nitrogen (N) and phosphorus (P). However, it is unclear how increased supplies of N and P will alter soil C sequestration, particularly in grasslands, which make up nearly a third of non‐agricultural land worldwide. Here, we leverage a globally distributed nutrient addition experiment (the Nutrient Network) to examine how a decade of N and P fertilization (alone and in combination) influenced soil C and N stocks at nine grassland sites spanning the continental United States. We measured changes in bulk soil C and N stocks and in three soil C fractions (light and heavy particulate organic matter, and mineral‐associated organic matter fractions). Nutrient amendment had variable effects on soil C and N pools that ranged from strongly positive to strongly negative, while soil C and N pool sizes varied by more than an order of magnitude across sites. Piecewise SEM clarified that small increases in plant C inputs with fertilization did not translate to greater soil C storage. Nevertheless, peak season aboveground plant biomass (but not root biomass or production) was strongly positively related to soil C storage at seven of the nine sites, and across all nine sites, soil C covaried with moisture index and soil mineralogy, regardless of fertilization. Overall, we show that site factors such as moisture index, plant productivity, soil texture, and mineralogy were key predictors of cross‐site soil C, while nutrient amendment had weaker and site‐specific effects on C sequestration. This suggests that prioritizing the protection of highly productive temperate grasslands is critical for reducing future greenhouse gas losses arising from land use change.

Pathogen transport amplifies or dilutes disease transmission depending on the host dose‐response relationship - Wee Hao Ng; Christopher R. Myers; Scott H. McArt; Stephen P. Ellner (Ecology Letters, 2022)
Pathogen transport by biotic or abiotic processes (e.g. mechanical vectors, wind, rain) can increase disease transmission by creating more opportunities for host exposure. But transport without replication has an inherent trade‐off, that creating new venues for exposure decreases the average pathogen abundance at each venue. The host dose‐response relationship is therefore required to correctly assess infection risk. We model and analyse two examples—biotic mechanical vectors in plant–pollinator networks, and abiotic‐facilitated long‐distance pathogen dispersal—to illustrate how oversimplifying the dose‐response relationship can lead to incorrect epidemiological predictions. When the minimum infective dose is high, mechanical vectors amplify disease transmission less than suggested by simple compartment models, and may even dilute transmission. When long‐distance dispersal leads to infrequent large exposures, models that assume a linear force of infection can substantially under‐predict the speed of epidemic spread. Our work highlights an important general interplay between dose‐response relationships and pathogen transport.

Measuring circulating triglycerides in free-living birds: evaluation of a field-usable point-of-care analyzer for American woodcock - Christopher M. Roelandt; Amber M. Roth; Scott R. McWilliams; Jill C. Witt (Journal of Ornithology, 2022)

TUBB3 Arg262His causes a recognizable syndrome including CFEOM3, facial palsy, joint contractures, and early-onset peripheral neuropathy - Mary C. Whitman; Brenda J. Barry; Caroline D. Robson; Flavia M. Facio; Carol Van Ryzin; Wai-Man Chan; Tanya J. Lehky; Audrey Thurm; Christopher Zalewski; Kelly A. King; Carmen Brewer; Konstantinia Almpani; et al. (Human Genetics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Climate mediates the relationship between plant biodiversity and forest structure across the United States - Christopher R. Hakkenberg; Scott J. Goetz (Global Ecology and Biogeography, 2021)
Aim Empirical biodiversity – forest structure relationships (BSRs) underlie the use of forest structure as a remotely sensible proxy of biodiversity. However, little is known about how BSRs generalize to continental scales or how climate interacts with structure to drive local patterns in plant diversity. Resolving these research gaps in macrosystems ecology will strengthen our understanding of the biogeography of plant diversity, with implications for global‐scale biodiversity mapping. Location USA. Time period Contemporary. Major taxa studied Vascular plants and trees. Methods We combined climate variables with field measurements and airborne lidar from all forest and woodland plots in the National Ecological Observatory Network (NEON) to characterize the role of climate in constraining BSRs across the United States. Spatial generalized linear mixed models were used to quantify the individual and joint effects of structure and climate on vascular plant and tree diversity. Results These findings provide evidence for broad‐scale BSRs across the USA; namely, between plant/tree diversity and forest structural metrics in the vertical and horizontal planes. Vascular plant diversity was positively related to horizontally heterogeneous and bottom‐skewed canopies, whereas tree diversity was positively associated with canopy cover and structural heterogeneity. In addition, climate variables related to stress (negatively), energy (positively) and seasonality (negatively) affected broad‐scale patterns in diversity, with water availability (but not temperature) exerting significant effects on structural conditions. Importantly, climate and structure interact to explain variance in BSRs along coldness, mean temperature and evapotranspiration gradients. Main conclusions Our findings reinforce the importance of local context dependence in assessing non‐stationary biogeographical patterns in forest biodiversity, as well as the unique ways that forest structure and climate interact to constrain plant diversity. Beyond these theoretical insights, this study provides an empirical foundation for generalizing remotely sensed estimates of climate and forest structure to model biodiversity over vast extents.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Contrasting population manipulations reveal resource competition between two large marsupials: bare-nosed wombats and eastern grey kangaroos - Julie Tamura; Janeane Ingram; Alynn M. Martin; Christopher P. Burridge; Scott Carver (Oecologia, 2021)

Improved Segmentation of the Intracranial and Ventricular Volumes in Populations with Cerebrovascular Lesions and Atrophy Using 3D CNNs - Emmanuel E. Ntiri; Melissa F. Holmes; Parisa M. Forooshani; Joel Ramirez; Fuqiang Gao; Miracle Ozzoude; Sabrina Adamo; Christopher J. M. Scott; Dar Dowlatshahi; Jane M. Lawrence-Dewar; Donna Kwan; Anthony E. Lang; et al. (Neuroinformatics, 2021)

Evaluation of the Effectiveness of Newer Helmet Designs with Emergent Shell and Padding Technologies Versus Older Helmet Models for Preserving White Matter Following a Season of High School Football - Jed A. Diekfuss; Weihong Yuan; Jonathan A. Dudley; Christopher A. DiCesare; Matthew B. Panzer; Thomas M. Talavage; Eric Nauman; Scott Bonnette; Alexis B. Slutsky-Ganesh; Joseph Clark; Manish Anand; Mekibib Altaye; et al. (Annals of Biomedical Engineering, 2021)

Performance of Multiple-Batch Approaches to Pharmacokinetic Bioequivalence Testing for Orally Inhaled Drug Products with Batch-to-Batch Variability - Elise Burmeister Getz; Kevin J. Carroll; J. David Christopher; Beth Morgan; Scott Haughie; Alessandro Cavecchi; Christopher Wiggenhorn; Hayden Beresford; Helen Strickland; Svetlana Lyapustina (AAPS PharmSciTech, 2021)
Batch-to-batch pharmacokinetic (PK) variability of orally inhaled drug products has been documented and can render single-batch PK bioequivalence (BE) studies unreliable; results from one batch may not be consistent with a repeated study using a different batch, yet the goal of PK BE is to deliver a product comparison that is interpretable beyond the specific batches used in the study. We characterized four multiple-batch PK BE approaches to improve outcome reliability without increasing the number of clinical study participants. Three approaches include multiple batches directly in the PK BE study with batch identity either excluded from the statistical model (“Superbatch”) or included as a fixed or random effect (“Fixed Batch Effect,” “Random Batch Effect”). A fourth approach uses a bio-predictive in vitro test to screen candidate batches, bringing the median batch of each product into the PK BE study (“Targeted Batch”). Three of these approaches (Fixed Batch Effect, Superbatch, Targeted Batch) continue the single-batch PK BE convention in which uncertainty in the Test/Reference ratio estimate due to batch sampling is omitted from the Test/Reference confidence interval. All three of these approaches provided higher power to correctly identify true bioequivalence than the standard single-batch approach with no increase in clinical burden. False equivalence (type I) error was inflated above the expected 5% level, but multiple batches controlled type I error better than a single batch. The Random Batch Effect approach restored 5% type I error, but had low power for small ( e.g. ,

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Human Actions Alter Tidal Marsh Seascapes and the Provision of Ecosystem Services - Ben L. Gilby; Michael P. Weinstein; Ronald Baker; Just Cebrian; Scott B. Alford; Ariella Chelsky; Denise Colombano; Rod M. Connolly; Carolyn A. Currin; Ilka C. Feller; Alyssa Frank; Janelle A. Goeke; et al. (Estuaries and Coasts, 2021)

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Short‐term exposure to silicon rapidly enhances plant resistance to herbivory - Jamie M. Waterman; Ximena Cibils‐Stewart; Christopher I. Cazzonelli; Susan E. Hartley; Scott N. Johnson (Ecology, 2021)
Silicon (Si) can adversely affect insect herbivores, particularly in plants that evolved the ability to accumulate large quantities of Si. Very rapid herbivore‐induced accumulation of Si has recently been demonstrated, but the level of protection against herbivory this affords plants remains unknown. Brachypodium distachyon , a model Si hyperaccumulating grass, was exposed to the chewing herbivore, Helicoverpa armigera, and grown under three conditions: supplied Si over 34 d (+Si), not supplied Si (−Si), or supplied Si once herbivory began (−Si → +Si). We evaluated the effectiveness of each Si treatment at reducing herbivore performance and measured Si‐based defenses and phenolics (another form of defense often reduced by Si). Although Si concentrations remained lower, within 72 h of exposure to Si, −Si → +Si plants were as resistant to herbivory as +Si plants. Both +Si and −Si → +Si treatments reduced herbivore damage and growth, and increased mandible wear compared to −Si. After 6 h, herbivory increased filled Si cell density in −Si → +Si plants, and within 24 h, −Si → +Si plants reached similar filled Si cell densities to +Si plants, although decreased phenolics only occurred in +Si plants. We demonstrate that plants with short‐term Si exposure can rapidly accumulate Si‐based antiherbivore defenses as effectively as plants with long‐term exposure.

A Decade of Incorporating Social Sciences in the Integrated Marine Biosphere Research Project (IMBeR): Much Done, Much to Do? - Ingrid van Putten; Rachel Kelly; Rachel D. Cavanagh; Eugene J. Murphy; Annette Breckwoldt; Stephanie Brodie; Christopher Cvitanovic; Mark Dickey-Collas; Lisa Maddison; Jess Melbourne-Thomas; Haritz Arrizabalaga; Kumiko Azetsu-Scott; et al. (Frontiers in Marine Science, 2021)
Successful management and mitigation of marine challenges depends on cooperation and knowledge sharing which often occurs across culturally diverse geographic regions. Global ocean science collaboration is therefore essential for developing global solutions. Building effective global research networks that can enable collaboration also need to ensure inter- and transdisciplinary research approaches to tackle complex marine socio-ecological challenges. To understand the contribution of interdisciplinary global research networks to solving these complex challenges, we use the Integrated Marine Biosphere Research (IMBeR) project as a case study. We investigated the diversity and characteristics of 1,827 scientists from 11 global regions who were attendees at different IMBeR global science engagement opportunities since 2009. We also determined the role of social science engagement in natural science based regional programmes (using key informants) and identified the potential for enhanced collaboration in the future. Event attendees were predominantly from western Europe, North America, and East Asia. But overall, in the global network, there was growing participation by females, students and early career researchers, and social scientists, thus assisting in moving toward interdisciplinarity in IMBeR research. The mainly natural science oriented regional programmes showed mixed success in engaging and collaborating with social scientists. This was mostly attributed to the largely natural science (i.e., biological, physical) goals and agendas of the programmes, and the lack of institutional support and push to initiate connections with social science. Recognising that social science research may not be relevant to all the aims and activities of all regional programmes, all researchers however, recognised the (potential) benefits of interdisciplinarity, which included broadening scientists’ understanding and perspectives, developing connections and interlinkages, and making science more useful. Pathways to achieve progress in regional programmes fell into four groups: specific funding, events to come together, within-programme-reflections, and social science champions. Future research programmes should have a strategic plan to be truly interdisciplinary, engaging natural and social sciences, as well as aiding early career professionals to actively engage in such programmes.

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

Anti‐herbivore silicon defences in a model grass are greatest under Miocene levels of atmospheric CO 2 - Fikadu N. Biru; Tarikul Islam; Ximena Cibils‐Stewart; Christopher I. Cazzonelli; Rivka Elbaum; Scott N. Johnson (Global Change Biology, 2021)
Silicon (Si) has an important role in mitigating diverse biotic and abiotic stresses in plants, mainly via the silicification of plant tissues. Environmental changes such as atmospheric CO 2 concentrations may affect grass Si concentrations which, in turn, can alter herbivore performance. We recently demonstrated that pre‐industrial atmospheric CO 2 increased Si accumulation in Brachypodium distachyon grass, yet the patterns of Si deposition in leaves and whether this affects insect herbivore performance remains unknown. Moreover, it is unclear whether CO 2 ‐driven changes in Si accumulation are linked to changes in gas exchange (e.g. transpiration rates). We therefore investigated how pre‐industrial (reduced; rCO 2 , 200 ppm), ambient (aCO 2 , 410 ppm) and elevated (eCO 2 , 640 ppm) CO 2 concentrations, in combination with Si‐treatment (Si+ or Si−), affected Si accumulation in B. distachyon and its subsequent effect on the performance of the global insect pest, Helicoverpa armigera . rCO 2 increased Si concentrations by 29% and 36% compared to aCO 2 and eCO 2 respectively. These changes were not related to observed changes in gas exchange under different CO 2 regimes, however. The increased Si accumulation under rCO 2 decreased herbivore relative growth rate (RGR) by 120% relative to eCO 2, whereas rCO 2 caused herbivore RGR to decrease by 26% compared to eCO 2 . Si supplementation also increased the density of macrohairs, silica and prickle cells, which was associated with reduced herbivore performance. There was a negative correlation among macrohair density, silica cell density, prickle cell density and herbivore RGR under rCO 2 suggesting that these changes in leaf surface morphology were linked to reduced performance under this CO 2 regime. To our knowledge, this is the first study to demonstrate that increased Si accumulation under pre‐industrial CO 2 reduces insect herbivore performance. Contrastingly, we found reduced Si accumulation under higher CO 2 , which suggests that some grasses may become more susceptible to insect herbivores under projected climate change scenarios.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Mapping Stresses on the Tibial Plateau Cartilage in an Ovine Model Using In-Vivo Gait Kinematics - Paris Vakiel; Mehdi Shekarforoush; Christopher R. Dennison; Michael Scott; Gregory Muench; David A. Hart; Nigel G. Shrive (Annals of Biomedical Engineering, 2021)

Leatherback Turtles in the Eastern Gulf of Mexico: Foraging and Migration Behavior During the Autumn and Winter - Christopher R. Sasso; Paul M. Richards; Scott R. Benson; Michael Judge; Nathan F. Putman; Derke Snodgrass; Brian A. Stacy (Frontiers in Marine Science, 2021)
We deployed 19 satellite tags on foraging adult leatherback turtles, including 17 females and 2 males, captured in the northeastern Gulf of Mexico in 2015, 2018, and 2019 in order to study regional distribution and movements. Prior to our study, limited data were available from leatherbacks foraging in the Gulf of Mexico. Tag deployment durations ranged from 63 to 247 days and turtles exhibited three distinct behavior types: foraging, transiting, or rapidly switching between foraging and transiting. Some females were tracked to nesting beaches in the Caribbean. Most of the leatherbacks remained on and foraged along the west Florida continental shelf whereas a few individuals foraged in waters of the central Gulf of Mexico during the autumn and winter. In addition, migration of adult females through the Yucatan Channel indicate that this is a seasonally important area for Caribbean nesting assemblages.

Correction to: Mapping Stresses on the Tibial Plateau Cartilage in an Ovine Model Using In-Vivo Gait Kinematics - Paris Vakiel; Mehdi Shekarforoush; Christopher R. Dennison; Michael Scott; Gregory Muench; David A. Hart; Nigel G. Shrive (Annals of Biomedical Engineering, 2021)

Measuring the Internal Stress in Ovine Meniscus During Simulated In Vivo Gait Kinematics: A Novel Method Using Fibre Optic Technology - Paris Vakiel; Christopher R. Dennison; Mehdi Shekarforoush; Michael Scott; David A. Hart; Nigel G. Shrive (Annals of Biomedical Engineering, 2021)

Targeted Application of Motor Learning Theory to Leverage Youth Neuroplasticity for Enhanced Injury-Resistance and Exercise Performance: OPTIMAL PREP - Jed A. Diekfuss; Dustin R. Grooms; Jennifer A. Hogg; Harjiv Singh; Alexis B. Slutsky-Ganesh; Scott Bonnette; Christopher Riehm; Manish Anand; Katharine S. Nissen; Gary B. Wilkerson; Gregory D. Myer (Journal of Science in Sport and Exercise, 2021)

Practical Training Strategies to Apply Neuro-Mechanistic Motor Learning Principles to Facilitate Adaptations Towards Injury-Resistant Movement in Youth - Jed A. Diekfuss; Scott Bonnette; Jennifer A. Hogg; Christopher Riehm; Dustin R. Grooms; Harjiv Singh; Manish Anand; Alexis B. Slutsky-Ganesh; Gary B. Wilkerson; Gregory D. Myer (Journal of Science in Sport and Exercise, 2021)

Early Ecosystem Development Varies With Elevation and Pre-Restoration Land Use/Land Cover in a Pacific Northwest Tidal Wetland Restoration Project - Christopher N. Janousek; Scott J. Bailey; Laura S. Brophy (Estuaries and Coasts, 2021)

Investigating potential toxic effects of pollutants on population growth rates and probability of extinction for a representative squamate - Scott M. Weir; Christopher J. Salice (Ecotoxicology, 2021)

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

Using GNSS radio occultation data to derive critical frequencies of the ionospheric sporadic E layer in real time - Bingkun Yu; Christopher J. Scott; Xianghui Xue; Xinan Yue; Xiankang Dou (GPS Solutions, 2021)
The small-scale electron density irregularities in the ionosphere have a significant impact on the interruptions of Global Navigation Satellite System (GNSS) navigation and the accuracy of GNSS positioning techniques. The sporadic ionospheric E (Es) layer significantly contributes to the transient interruptions of signals (loss of lock) for GNSS tracking loops. These effects on the GNSS radio occultation (RO) signals can be used to derive the global location and intensity of Es layers as a complement to ground-based observations. Here we conduct statistical analyses of the intensity of Es layers, based on the scintillation index S4max from the FORMOSAT-3/COSMIC during the period 2006–2014. In comparison with simultaneous observations from an ionosonde network of five low-to-middle latitude ionosondes, the S4max indices from COSMIC, especially the small values, are linearly related to the critical frequency of Es layers (f o Es). An accumulated period of less than 1 h is required to derive the short-term variations in real-time ionospheric Es layers. A total of 30.22%, 69.57% and 98.13% coincident hourly f o Es values have a relative difference less than 10%, 30% and 100%. Overall, the GNSS RO measurements have the potential to provide accurate hourly observations of Es layers. Observations with S4max < 0.4 (f o Es < 3.6 MHz), accounting for 66% of COSMIC S4 measurements, have not been used fully previously, as they are not easily visible in ground-based ionosonde data.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Stress Measurements on the Articular Cartilage Surface Using Fiber Optic Technology and In-Vivo Gait Kinematics - Paris Vakiel; Mehdi Shekarforoush; Christopher R. Dennison; Michael Scott; Cyril B. Frank; David A. Hart; Nigel G. Shrive (Annals of Biomedical Engineering, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Relationship between synoptic weather type and emergency department visits for different types of pain across the Triangle region of North Carolina - Christopher Elcik; Christopher M. Fuhrmann; Scott C. Sheridan; Andrew E. Mercer; Kathleen Sherman-Morris (International Journal of Biometeorology, 2020)

Correction to: Acute aquatic toxicity of tire and road wear particles to alga, daphnid, and fish - Christopher Marwood; Britt McAtee; Marisa Kreider; R. Scott Ogle; Brent Finley; Len Sweet; Julie Panko (Ecotoxicology, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Progress in Operational Modeling in Support of Oil Spill Response - Christopher H. Barker; Vassiliki H. Kourafalou; CJ Beegle-Krause; Michel Boufadel; Mark A. Bourassa; Steve G. Buschang; Yannis Androulidakis; Eric P. Chassignet; Knut-Frode Dagestad; Donald G. Danmeier; Anusha L. Dissanayake; Jerry A. Galt; et al. (Journal of Marine Science and Engineering, 2020)
Following the 2010 Deepwater Horizon accident of a massive blow-out in the Gulf of Mexico, scientists from government, industry, and academia collaborated to advance oil spill modeling and share best practices in model algorithms, parameterizations, and application protocols. This synergy was greatly enhanced by research funded under the Gulf of Mexico Research Initiative (GoMRI), a 10-year enterprise that allowed unprecedented collection of observations and data products, novel experiments, and international collaborations that focused on the Gulf of Mexico, but resulted in the generation of scientific findings and tools of broader value. Operational oil spill modeling greatly benefited from research during the GoMRI decade. This paper provides a comprehensive synthesis of the related scientific advances, remaining challenges, and future outlook. Two main modeling components are discussed: Ocean circulation and oil spill models, to provide details on all attributes that contribute to the success and limitations of the integrated oil spill forecasts. These forecasts are discussed in tandem with uncertainty factors and methods to mitigate them. The paper focuses on operational aspects of oil spill modeling and forecasting, including examples of international operational center practices, observational needs, communication protocols, and promising new methodologies.

Landscape simplification shapes pathogen prevalence in plant‐pollinator networks - Laura L. Figueroa; Heather Grab; Wee Hao Ng; Christopher R. Myers; Peter Graystock; Quinn S. McFrederick; Scott H. McArt (Ecology Letters, 2020)
Species interaction networks, which play an important role in determining pathogen transmission and spread in ecological communities, can shift in response to agricultural landscape simplification. However, we know surprisingly little about how landscape simplification‐driven changes in network structure impact epidemiological patterns. Here, we combine mathematical modelling and data from eleven bipartite plant‐pollinator networks observed along a landscape simplification gradient to elucidate how changes in network structure shape disease dynamics. Our empirical data show that landscape simplification reduces pathogen prevalence in bee communities via increased diet breadth of the dominant species. Furthermore, our empirical data and theoretical model indicate that increased connectance reduces the likelihood of a disease outbreak and decreases variance in prevalence among bee species in the community, resulting in a dilution effect. Because infectious diseases are implicated in pollinator declines worldwide, a better understanding of how land use change impacts species interactions is therefore critical for conserving pollinator health.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Adaptable Monitoring Package Development and Deployment: Lessons Learned for Integrated Instrumentation at Marine Energy Sites - Brian Polagye; James Joslin; Paul Murphy; Emma Cotter; Mitchell Scott; Paul Gibbs; Christopher Bassett; Andrew Stewart (Journal of Marine Science and Engineering, 2020)
Integrated instrumentation packages are an attractive option for environmental and ecological monitoring at marine energy sites, as they can support a range of sensors in a form factor compact enough for the operational constraints posed by energetic waves and currents. Here we present details of the architecture and performance for one such system—the Adaptable Monitoring Package—which supports active acoustic, passive acoustic, and optical sensing to quantify the physical environment and animal presence at marine energy sites. we describe cabled and autonomous deployments and contrast the relatively limited system capabilities in an autonomous operating mode with more expansive capabilities, including real-time data processing, afforded by shore power or in situ power harvesting from waves. Across these deployments, we describe sensor performance, outcomes for biological target classification algorithms using data from multibeam sonars and optical cameras, and the effectiveness of measures to limit biofouling and corrosion. On the basis of these experiences, we discuss the demonstrated requirements for integrated instrumentation, possible operational concepts for monitoring the environmental and ecological effects of marine energy converters using such systems, and the engineering trade-offs inherent in their development. Overall, we find that integrated instrumentation can provide powerful capabilities for observing rare events, managing the volume of data collected, and mitigating potential bias to marine animal behavior. These capabilities may be as relevant to the broader oceanographic community as they are to the emerging marine energy sector.

Quantifying storm surge and risk reduction costs: a case study for Lafitte, Louisiana - Christopher G. Siverd; Scott C. Hagen; Matthew V. Bilskie; DeWitt H. Braud; Robert R. Twilley (Climatic Change, 2020)

Phylogenomics reveals conservation challenges and opportunities for cryptic endangered species in a rapidly disappearing desert ecosystem - Daniel Rubinoff; J. Bradley Reil; Kendall H. Osborne; Christopher J. Gregory; Scott M. Geib; Julian R. Dupuis (Biodiversity and Conservation, 2020)

Differential Bioaccumulation of Mercury and Selenium in Stomach Contents and Tissues of Three Colorado, USA, Cutthroat Trout Populations - Scott J. Herrmann; Del Wayne R. Nimmo; James S. Carsella; Igor V. Melnykov; Christopher M. Kennedy; Kevin B. Rogers; Lynn M. Herrmann-Hoesing (Bulletin of Environmental Contamination and Toxicology, 2020)

Informing management decisions for ecological networks, using dynamic models calibrated to noisy time‐series data - Matthew P. Adams; Scott A. Sisson; Kate J. Helmstedt; Christopher M. Baker; Matthew H. Holden; Michaela Plein; Jacinta Holloway; Kerrie L. Mengersen; Eve McDonald‐Madden (Ecology Letters, 2020)
Well‐intentioned environmental management can backfire, causing unforeseen damage. To avoid this, managers and ecologists seek accurate predictions of the ecosystem‐wide impacts of interventions, given small and imprecise datasets, which is an incredibly difficult task. We generated and analysed thousands of ecosystem population time series to investigate whether fitted models can aid decision‐makers to select interventions. Using these time‐series data (sparse and noisy datasets drawn from deterministic Lotka‐Volterra systems with two to nine species, of known network structure), dynamic model forecasts of whether a species’ future population will be positively or negatively affected by rapid eradication of another species were correct > 70% of the time. Although 70% correct classifications is only slightly better than an uninformative prediction (50%), this classification accuracy can be feasibly improved by increasing monitoring accuracy and frequency. Our findings suggest that models may not need to produce well‐constrained predictions before they can inform decisions that improve environmental outcomes.

Corrigendum: The Unknown and the Unexplored: Insights Into the Pacific Deep-Sea Following NOAA CAPSTONE Expeditions - Brian R. C. Kennedy; Kasey Cantwell; Mashkoor Malik; Christopher Kelley; Jeremy Potter; Kelley Elliott; Elizabeth Lobecker; Lindsay McKenna Gray; Derek Sowers; Michael P. White; Scott C. France; Steven Auscavitch; et al. (Frontiers in Marine Science, 2020)

Northern quahog ( Mercenaria mercenaria ) larval transport and settlement modeled for a temperate estuary - M. Conor McManus; David S. Ullman; Scott D. Rutherford; Christopher Kincaid (Limnology and Oceanography, 2020)
Evaluating marine species' population connectivity through larval transport can provide insight into the reliance of geographically separated areas on each other's recruitment and metapopulation resiliency. Using larval transport modeling, we assessed the significance of different regions in supporting the Narragansett Bay Northern quahog ( Mercenaria mercenaria ) population. We aimed to identify how areas with varying adult quahog biomass and implemented management strategies (based on water quality and commercial harvest) contribute to the overall stock's larval supply. Larval trajectories were modeled by integrating the currents from a realistic physical circulation model with quahog larval behavior applied to particles during spawning periods of 2006, 2007, and 2014. Modeled larval transport suggested that settlement occurs throughout Narragansett Bay, with 35% of spawned larvae swept out of the Bay to the coastal ocean and leaving the stock bounds. Quahogs in areas where shellfishing is prohibited due to water quality concerns produce a significant portion of the Bay's spawned larvae, theoretically serving as de facto spawning sanctuaries. The Providence River, located at the head of the Bay with high mature quahog biomass and currently closed to fishing due to water quality, is a significant source of quahog larvae for the stock. Simulated larval quahog settlement locations corresponded predominantly to sandy bottoms, with less spatial correspondence to commercial fisheries landings. Our work provides insight into the population connectivity of quahogs in Narragansett Bay and highlights the importance of considering oceanography and species' life history characteristics when constructing effective fisheries management plans.

Using Ship-Deployed High-Endurance Unmanned Aerial Vehicles for the Study of Ocean Surface and Atmospheric Boundary Layer Processes - Christopher J. Zappa; Scott M. Brown; Nathan J. M. Laxague; Tejendra Dhakal; Ryan A. Harris; Aaron M. Farber; Ajit Subramaniam (Frontiers in Marine Science, 2020)

Capacity of United States federal government and its partners to rapidly and accurately report the identity (taxonomy) of non-native organisms intercepted in early detection programs - Christopher H. C. Lyal; Scott E. Miller (Biological Invasions, 2020)
The early detection of and rapid response to invasive species (EDRR) depends on accurate and rapid identification of non-native species. The 2016–2018 National Invasive Species Council Management Plan called for an assessment of US government (federal) capacity to report on the identity of non-native organisms intercepted through early detection programs. This paper serves as the response to that action item. Here we summarize survey-based findings and make recommendations for improving the federal government’s capacity to identify non-native species authoritatively in a timely manner. We conclude with recommendations to improve accurate identification within the context of EDRR by increasing coordination, maintaining taxonomic expertise, creating an identification tools clearinghouse, developing and using taxonomic standards for naming and identification protocols, expanding the content of DNA and DNA Barcode libraries, ensuring long-term sustainability of biological collections, and engaging and empowering citizens and citizen science groups.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Coastal Louisiana landscape and storm surge evolution: 1850–2110 - Christopher G. Siverd; Scott C. Hagen; Matthew V. Bilskie; DeWitt H. Braud; R. Hampton Peele; Madeline R. Foster-Martinez; Robert R. Twilley (Climatic Change, 2019)

Urbanization reduces genetic connectivity in bobcats ( Lynx rufus ) at both intra– and interpopulation spatial scales - Christopher P. Kozakiewicz; Christopher P. Burridge; W. Chris Funk; Patricia E. Salerno; Daryl R. Trumbo; Roderick B. Gagne; Erin E. Boydston; Robert N. Fisher; Lisa M. Lyren; Megan K. Jennings; Seth P. D. Riley; Laurel E. K. Serieys; et al. (Molecular Ecology, 2019)
Urbanization is a major factor driving habitat fragmentation and connectivity loss in wildlife. However, the impacts of urbanization on connectivity can vary among species and even populations due to differences in local landscape characteristics, and our ability to detect these relationships may depend on the spatial scale at which they are measured. Bobcats ( Lynx rufus ) are relatively sensitive to urbanization and the status of bobcat populations is an important indicator of connectivity in urban coastal southern California. We genotyped 271 bobcats at 13,520 SNP loci to conduct a replicated landscape resistance analysis in five genetically distinct populations. We tested urban and natural factors potentially influencing individual connectivity in each population separately, as well as study–wide. Overall, landscape genomic effects were most frequently detected at the study–wide spatial scale, with urban land cover (measured as impervious surface) having negative effects and topographic roughness having positive effects on gene flow. The negative effect of urban land cover on connectivity was also evident when populations were analyzed separately despite varying substantially in spatial area and the proportion of urban development, confirming a pervasive impact of urbanization largely independent of spatial scale. The effect of urban development was strongest in one population where stream habitat had been lost to development, suggesting that riparian corridors may help mitigate reduced connectivity in urbanizing areas. Our results demonstrate the importance of replicating landscape genetic analyses across populations and considering how landscape genetic effects may vary with spatial scale and local landscape structure.

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Urbanization impacts apex predator gene flow but not genetic diversity across an urban‐rural divide - Daryl R. Trumbo; Patricia E. Salerno; Kenneth A. Logan; Mathew W. Alldredge; Roderick B. Gagne; Christopher P. Kozakiewicz; Simona Kraberger; Nicholas M. Fountain‐Jones; Meggan E. Craft; Scott Carver; Holly B. Ernest; Kevin R. Crooks; et al. (Molecular Ecology, 2019)
Apex predators are important indicators of intact natural ecosystems. They are also sensitive to urbanization because they require broad home ranges and extensive contiguous habitat to support their prey base. Pumas ( Puma concolor ) can persist near human developed areas, but urbanization may be detrimental to their movement ecology, population structure, and genetic diversity. To investigate potential effects of urbanization in population connectivity of pumas, we performed a landscape genomics study of 130 pumas on the rural Western Slope and more urbanized Front Range of Colorado, USA. Over 12,000 single nucleotide polymorphisms (SNPs) were genotyped using double‐digest, restriction site‐associated DNA sequencing (ddRADseq). We investigated patterns of gene flow and genetic diversity, and tested for correlations between key landscape variables and genetic distance to assess the effects of urbanization and other landscape factors on gene flow. Levels of genetic diversity were similar for the Western Slope and Front Range, but effective population sizes were smaller, genetic distances were higher, and there was more admixture in the more urbanized Front Range. Forest cover was strongly positively associated with puma gene flow on the Western Slope, while impervious surfaces restricted gene flow and more open, natural habitats enhanced gene flow on the Front Range. Landscape genomic analyses revealed differences in puma movement and gene flow patterns in rural versus urban settings. Our results highlight the utility of dense, genome‐scale markers to document subtle impacts of urbanization on a wide‐ranging carnivore living near a large urban center.

Extracellular superoxide production by key microbes in the global ocean - Kevin M. Sutherland; Allison Coe; Rebecca J. Gast; Sydney Plummer; Christopher P. Suffridge; Julia M. Diaz; Jeff S. Bowman; Scott D. Wankel; Colleen M. Hansel (Limnology and Oceanography, 2019)
Bacteria and eukaryotes produce the reactive oxygen species superoxide both within and outside the cell. Although superoxide is typically associated with the detrimental and sometimes fatal effects of oxidative stress, it has also been shown to be involved in a range of essential biochemical processes, including cell signaling, growth, differentiation, and defense. Light‐independent extracellular superoxide production has been shown to be widespread among many marine heterotrophs and phytoplankton, but the extent to which this trait is relevant to marine microbial physiology and ecology throughout the global ocean is unknown. Here, we investigate the dark extracellular superoxide production of five groups of organisms that are geographically widespread and represent some of the most abundant organisms in the global ocean. These include Prochlorococcus , Synechococcus , Pelagibacter , Phaeocystis , and Geminigera . Cell‐normalized net extracellular superoxide production rates ranged seven orders of magnitude, from undetectable to 14,830 amol cell −1 h −1 , with the cyanobacterium Prochlorococcus being the lowest producer and the cryptophyte Geminigera being the most prolific producer. Extracellular superoxide production exhibited a strong inverse relationship with cell number, pointing to a potential role in cell signaling. We demonstrate that rapid, cell‐number–dependent changes in the net superoxide production rate by Synechococcus and Pelagibacter arose primarily from changes in gross production of extracellular superoxide, not decay. These results expand the relevance of dark extracellular superoxide production to key marine microbes of the global ocean, suggesting that superoxide production in marine waters is regulated by a diverse suite of marine organisms in both dark and sunlit waters.

Associations of mammographic breast density with breast stem cell marker-defined breast cancer subtypes - Lusine Yaghjyan; Ashwini K. Esnakula; Christopher G. Scott; Akemi T. Wijayabahu; Matthew R. Jensen; Celine M. Vachon (Cancer Causes & Control, 2019)

A highly resolved food web for insect seed predators in a species‐rich tropical forest - Sofia Gripenberg; Yves Basset; Owen T. Lewis; J. Christopher D. Terry; S. Joseph Wright; Indira Simón; D. Catalina Fernández; Marjorie Cedeño‐Sanchez; Marleny Rivera; Héctor Barrios; John W. Brown; Osvaldo Calderón; et al. (Ecology Letters, 2019)
The top‐down and indirect effects of insects on plant communities depend on patterns of host use, which are often poorly documented, particularly in species‐rich tropical forests. At Barro Colorado Island, Panama, we compiled the first food web quantifying trophic interactions between the majority of co‐occurring woody plant species and their internally feeding insect seed predators. Our study is based on more than 200 000 fruits representing 478 plant species, associated with 369 insect species. Insect host‐specificity was remarkably high: only 20% of seed predator species were associated with more than one plant species, while each tree species experienced seed predation from a median of two insect species. Phylogeny, but not plant traits, explained patterns of seed predator attack. These data suggest that seed predators are unlikely to mediate indirect interactions such as apparent competition between plant species, but are consistent with their proposed contribution to maintaining plant diversity via the Janzen–Connell mechanism.

Pattern and scale: evaluating generalities in crab distributions and marsh dynamics from small plots to a national scale - Kerstin Wasson; Kenneth Raposa; Monica Almeida; Kathryn Beheshti; Jeffrey A. Crooks; Anna Deck; Nikki Dix; Caitlin Garvey; Jason Goldstein; David Samuel Johnson; Scott Lerberg; Pamela Marcum; et al. (Ecology, 2019)
The generality of ecological patterns depends inextricably on the scale at which they are examined. We investigated patterns of crab distribution and the relationship between crabs and vegetation in salt marshes at multiple scales. By using consistent monitoring protocols across 15 U.S. National Estuarine Research Reserves, we were able to synthesize patterns from the scale of quadrats to the entire marsh landscape to regional and national scales. Some generalities emerged across marshes from our overall models, and these are useful for informing broad coastal management policy. We found that crab burrow distribution within a marsh could be predicted by marsh elevation, distance to creek and soil compressibility. While these physical factors also affected marsh vegetation cover, we did not find a strong or consistent overall effect of crabs at a broad scale in our multivariate model, though regressions conducted separately for each site revealed that crab burrows were negatively correlated with vegetation cover at 4 out of 15 sites. This contrasts with recent smaller‐scale studies and meta‐analyses synthesizing such studies that detected strong negative effects of crabs on marshes, likely because we sampled across the entire marsh landscape, while targeted studies are typically limited to low‐lying areas near creeks, where crab burrow densities are highest. Our results suggest that sea‐level rise generally poses a bigger threat to marshes than crabs, but there will likely be interactions between these physical and biological factors. Beyond these generalities across marshes, we detected some regional differences in crab community composition, richness, and abundance. However, we found striking differences among sites within regions, and within sites, in terms of crab abundance and relationships to marsh integrity. Although generalities are broadly useful, our findings indicate that local managers cannot rely on data from other nearby systems, but rather need local information for developing salt marsh management strategies.

The Unknown and the Unexplored: Insights Into the Pacific Deep-Sea Following NOAA CAPSTONE Expeditions - Brian R. C. Kennedy; Kasey Cantwell; Mashkoor Malik; Christopher Kelley; Jeremy Potter; Kelley Elliott; Elizabeth Lobecker; Lindsay McKenna Gray; Derek Sowers; Michael P. White; Scott C. France; Steven Auscavitch; et al. (Frontiers in Marine Science, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

In situ Autonomous Acquisition and Preservation of Marine Environmental DNA Using an Autonomous Underwater Vehicle - Kevan M. Yamahara; Christina M. Preston; James Birch; Kristine Walz; Roman Marin; Scott Jensen; Douglas Pargett; Brent Roman; William Ussler; Yanwu Zhang; John Ryan; Brett Hobson; et al. (Frontiers in Marine Science, 2019)

Building the Knowledge-to-Action Pipeline in North America: Connecting Ocean Acidification Research and Actionable Decision Support - Jessica N. Cross; Jessie A. Turner; Sarah R. Cooley; Jan A. Newton; Kumiko Azetsu-Scott; R. Christopher Chambers; Darcy Dugan; Kaitlin Goldsmith; Helen Gurney-Smith; Alexandra R. Harper; Elizabeth B. Jewett; Denise Joy; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Assessing the Effects of Climate Change and Air Pollution on Soil Properties and Plant Diversity in Northeastern U.S. Hardwood Forests: Model Setup and Evaluation - Salim Belyazid; Jennifer Phelan; Bengt Nihlgård; Harald Sverdrup; Charles Driscoll; Ivan Fernandez; Julian Aherne; Leslie M. Teeling-Adams; Scott Bailey; Matt Arsenault; Natalie Cleavitt; Brett Engstrom; et al. (Water, Air, & Soil Pollution, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Lack of consistent sex differences in d-amphetamine-induced dopamine release measured with [18F]fallypride PET - Christopher T. Smith; Linh C. Dang; Leah L. Burgess; Scott F. Perkins; M. Danica San Juan; Darcy K. Smith; Ronald L. Cowan; Nam T. Le; Robert M. Kessler; Gregory R. Samanez-Larkin; David H. Zald (Psychopharmacology, 2019)

Development and Implementation of a Continuing Medical Education Program in Canada: Knowledge Translation for Renal Cell Carcinoma (KT4RCC) - Luke T. Lavallée; Ryan Fitzpatrick; Lori A. Wood; Joan Basiuk; Christopher Knee; Sonya Cnossen; Ranjeeta Mallick; Kelsey Witiuk; Marie Vanhuyse; Simon Tanguay; Antonio Finelli; Michael A. S. Jewett; et al. (Journal of Cancer Education, 2019)

Assessing livelihood-ecosystem interdependencies and natural resource governance in Indian villages in the Middle Himalayas - Mark Everard; Nishikant Gupta; Christopher A. Scott; Prakash C. Tiwari; Bhagwati Joshi; Gaurav Kataria; Smita Kumar (Regional Environmental Change, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Dichomitus squalens partially tailors its molecular responses to the composition of solid wood - Paul Daly; Sara Casado López; Mao Peng; Christopher S. Lancefield; Samuel O. Purvine; Young‐Mo Kim; Erika M. Zink; Alice Dohnalkova; Vasanth R. Singan; Anna Lipzen; David Dilworth; Mei Wang; et al. (Environmental Microbiology, 2018)
Summary White‐rot fungi, such as Dichomitus squalens , degrade all wood components and inhabit mixed‐wood forests containing both soft‐ and hardwood species. In this study, we evaluated how D. squalens responded to the compositional differences in softwood [guaiacyl (G) lignin and higher mannan content] and hardwood [syringyl/guaiacyl (S/G) lignin and higher xylan content] using semi‐natural solid cultures. Spruce (softwood) and birch (hardwood) sticks were degraded by D. squalens as measured by oxidation of the lignins using 2D‐NMR. The fungal response as measured by transcriptomics, proteomics and enzyme activities showed a partial tailoring to wood composition. Mannanolytic transcripts and proteins were more abundant in spruce cultures, while a proportionally higher xylanolytic activity was detected in birch cultures. Both wood types induced manganese peroxidases to a much higher level than laccases, but higher transcript and protein levels of the manganese peroxidases were observed on the G‐lignin rich spruce. Overall, the molecular responses demonstrated a stronger adaptation to the spruce rather than birch composition, possibly because D. squalens is mainly found degrading softwoods in nature, which supports the ability of the solid wood cultures to reflect the natural environment.

A jugular vein compression collar prevents alterations of endogenous electrocortical dynamics following blast exposure during special weapons and tactical (SWAT) breacher training - Scott Bonnette; Jed A. Diekfuss; Adam W. Kiefer; Michael A. Riley; Kim D. Barber Foss; Staci Thomas; Christopher A. DiCesare; Weihong Yuan; Jonathan Dudley; Amit Reches; Gregory D. Myer (Experimental Brain Research, 2018)

Long‐term nitrogen fertilization decreases bacterial diversity and favors the growth of Actinobacteria and Proteobacteria in agro‐ecosystems across the globe - Zhongmin Dai; Weiqin Su; Huaihai Chen; Albert Barberán; Haochun Zhao; Mengjie Yu; Lu Yu; Philip C. Brookes; Christopher W. Schadt; Scott X. Chang; Jianming Xu (Global Change Biology, 2018)
Long‐term elevated nitrogen (N) input from anthropogenic sources may cause soil acidification and decrease crop yield, yet the response of the belowground microbial community to long‐term N input alone or in combination with phosphorus (P) and potassium (K) is poorly understood. We explored the effect of long‐term N and NPK fertilization on soil bacterial diversity and community composition using meta‐analysis of a global dataset. Nitrogen fertilization decreased soil pH , and increased soil organic carbon (C) and available N contents. Bacterial taxonomic diversity was decreased by N fertilization alone, but was increased by NPK fertilization. The effect of N fertilization on bacterial diversity varied with soil texture and water management, but was independent of crop type or N application rate. Changes in bacterial diversity were positively related to both soil pH and organic C content under N fertilization alone, but only to soil organic C under NPK fertilization. Microbial biomass C decreased with decreasing bacterial diversity under long‐term N fertilization. Nitrogen fertilization increased the relative abundance of Proteobacteria and Actinobacteria , but reduced the abundance of Acidobacteria , consistent with the general life history strategy theory for bacteria. The positive correlation between N application rate and the relative abundance of Actinobacteria indicates that increased N availability favored the growth of Actinobacteria . This first global analysis of long‐term N and NPK fertilization that differentially affects bacterial diversity and community composition provides a reference for nutrient management strategies for maintaining belowground microbial diversity in agro‐ecosystems worldwide.

How small an island? Speciation by endemic mammals ( Apomys , Muridae) on an oceanic Philippine island - Lawrence R. Heaney; Christopher C. Kyriazis; Danilo S. Balete; Scott J. Steppan; Eric A. Rickart (Journal of Biogeography, 2018)
Aim To investigate the influence of oceanic island area on speciation by small mammals, in the context of other land vertebrates. Location Mindoro Island (9,735 km 2 ), an oceanic island in the Philippines. Methods Extensive field surveys on Mindoro, followed by sequencing one mitochondrial and three nuclear genes for use in phylogenetic, population genetic and coalescent‐based analyses, and by morphometric analysis of craniodental data. Results Our analyses documented the presence on Mindoro of an endemic clade of probably four species of Apomys , subgenus Megapomys . The common ancestor likely arrived from Luzon Island across a narrow sea channel between 2.4 and 1.5 Ma; the four probable species occur allopatrically, with variation in their ranges along elevational gradients. Mindoro thus becomes the smallest oceanic island on which speciation by small mammals has been documented. Main conclusions A review of land‐living vertebrates suggests that bats and large mammals have the greatest area requirements for speciation, whereas frogs, lizards, birds and small mammals have lower and similar minimum area requirements. However, with the exception of Anolis lizards, data are scattered and limited; much research is needed to document the impact of island area on speciation. The existence of a lower limit implies that the biological processes that influence species richness do not operate equivalently along a gradient of island areas: speciation within islands may not contribute to changes in species richness below some limit, unlike colonization and extinction, which operate at all island sizes.

Comparative, collaborative, and integrative risk governance for emerging technologies - Igor Linkov; Benjamin D. Trump; Elke Anklam; David Berube; Patrick Boisseasu; Christopher Cummings; Scott Ferson; Marie-Valentine Florin; Bernard Goldstein; Danail Hristozov; Keld Alstrup Jensen; Georgios Katalagarianakis; et al. (Environment Systems and Decisions, 2018)

Drought adaptation and development: small-scale irrigated agriculture in northeast Brazil - Lauren Herwehe; Christopher A. Scott (Climate and Development, 2018)

Correction to: PK–PD Compass: bringing infectious diseases pharmacometrics to the patient’s bedside - Catharine C. Bulik; Justin C. Bader; Li Zhang; Scott A. Van Wart; Christopher M. Rubino; Sujata M. Bhavnani; Kim L. Sweeney; Paul G. Ambrose (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Estimating Base Cation Weathering Rates in the USA: Challenges of Uncertain Soil Mineralogy and Specific Surface Area with Applications of the PROFILE Model - Colin J. Whitfield; Jennifer N. Phelan; John Buckley; Christopher M. Clark; Scott Guthrie; Jason A. Lynch (Water, Air, & Soil Pollution, 2018)

Automated Image Analysis of Offshore Infrastructure Marine Biofouling - Kate Gormley; Faron McLellan; Christopher McCabe; Claire Hinton; Joseph Ferris; David Kline; Beth Scott (Journal of Marine Science and Engineering, 2018)
In the UK, some of the oldest oil and gas installations have been in the water for over 40 years and have considerable colonisation by marine organisms, which may lead to both industry challenges and/or potential biodiversity benefits (e.g., artificial reefs). The project objective was to test the use of an automated image analysis software (CoralNet) on images of marine biofouling from offshore platforms on the UK continental shelf, with the aim of (i) training the software to identify the main marine biofouling organisms on UK platforms; (ii) testing the software performance on 3 platforms under 3 different analysis criteria (methods A–C); (iii) calculating the percentage cover of marine biofouling organisms and (iv) providing recommendations to industry. Following software training with 857 images, and testing of three platforms, results showed that diversity of the three platforms ranged from low (in the central North Sea) to moderate (in the northern North Sea). The two central North Sea platforms were dominated by the plumose anemone Metridium dianthus; and the northern North Sea platform showed less obvious species domination. Three different analysis criteria were created, where the method of selection of points, number of points assessed and confidence level thresholds (CT) varied: (method A) random selection of 20 points with CT 80%, (method B) stratified random of 50 points with CT of 90% and (method C) a grid approach of 100 points with CT of 90%. Performed across the three platforms, the results showed that there were no significant differences across the majority of species and comparison pairs. No significant difference (across all species) was noted between confirmed annotations methods (A, B and C). It was considered that the software performed well for the classification of the main fouling species in the North Sea. Overall, the study showed that the use of automated image analysis software may enable a more efficient and consistent approach to marine biofouling analysis on offshore structures; enabling the collection of environmental data for decommissioning and other operational industries.

Evaluating Tidal Wetland Restoration Performance Using National Estuarine Research Reserve System Reference Sites and the Restoration Performance Index (RPI) - Kenneth B. Raposa; Scott Lerberg; Craig Cornu; John Fear; Nina Garfield; Christopher Peter; Robin L.J. Weber; Gregg Moore; David Burdick; Michelle Dionne (Estuaries and Coasts, 2018)

Range position and climate sensitivity: The structure of among‐population demographic responses to climatic variation - Staci M. Amburgey; David A. W. Miller; Evan H. Campbell Grant; Tracy A. G. Rittenhouse; Michael F. Benard; Jonathan L. Richardson; Mark C. Urban; Ward Hughson; Adrianne B. Brand; Christopher J. Davis; Carmen R. Hardin; Peter W. C. Paton; et al. (Global Change Biology, 2018)
Species’ distributions will respond to climate change based on the relationship between local demographic processes and climate and how this relationship varies based on range position. A rarely tested demographic prediction is that populations at the extremes of a species’ climate envelope (e.g., populations in areas with the highest mean annual temperature) will be most sensitive to local shifts in climate (i.e., warming). We tested this prediction using a dynamic species distribution model linking demographic rates to variation in temperature and precipitation for wood frogs ( Lithobates sylvaticus ) in North America. Using long‐term monitoring data from 746 populations in 27 study areas, we determined how climatic variation affected population growth rates and how these relationships varied with respect to long‐term climate. Some models supported the predicted pattern, with negative effects of extreme summer temperatures in hotter areas and positive effects on recruitment for summer water availability in drier areas. We also found evidence of interacting temperature and precipitation influencing population size, such as extreme heat having less of a negative effect in wetter areas. Other results were contrary to predictions, such as positive effects of summer water availability in wetter parts of the range and positive responses to winter warming especially in milder areas. In general, we found wood frogs were more sensitive to changes in temperature or temperature interacting with precipitation than to changes in precipitation alone. Our results suggest that sensitivity to changes in climate cannot be predicted simply by knowing locations within the species’ climate envelope. Many climate processes did not affect population growth rates in the predicted direction based on range position. Processes such as species‐interactions, local adaptation, and interactions with the physical landscape likely affect the responses we observed. Our work highlights the need to measure demographic responses to changing climate.

Examination of dogbane beetle (Chrysochus auratus) feeding and phenology on spreading dogbane, and considerations for biological control - Megan C. MacEachern-Balodis; Nathan S. Boyd; Scott N. White; G. Christopher Cutler (Arthropod-Plant Interactions, 2017)

The Quest to Develop Ecogenomic Sensors: A 25-Year History of the Environmental Sample Processor (ESP) as a Case Study - Christopher Scholin; James Birch; Scott Jensen; Roman Marin III; Eugene Massion; Douglas Pargett; Christina Preston; Brent Roman; William Ussler III (Oceanography, 2017)

Signatures of polygenic adaptation associated with climate across the range of a threatened fish species with high genetic connectivity - Katherine A. Harrisson; Stephen J. Amish; Alexandra Pavlova; Shawn R. Narum; Marina Telonis‐Scott; Meaghan L. Rourke; Jarod Lyon; Zeb Tonkin; Dean M. Gilligan; Brett A. Ingram; Mark Lintermans; Han Ming Gan; et al. (Molecular Ecology, 2017)
Adaptive differences across species’ ranges can have important implications for population persistence and conservation management decisions. Despite advances in genomic technologies, detecting adaptive variation in natural populations remains challenging. Key challenges in gene–environment association studies involve distinguishing the effects of drift from those of selection and identifying subtle signatures of polygenic adaptation. We used paired‐end restriction site‐associated DNA sequencing data (6,605 biallelic single nucleotide polymorphisms; SNP s) to examine population structure and test for signatures of adaptation across the geographic range of an iconic Australian endemic freshwater fish species, the Murray cod Maccullochella peelii . Two univariate gene–association methods identified 61 genomic regions associated with climate variation. We also tested for subtle signatures of polygenic adaptation using a multivariate method (redundancy analysis; RDA ). The RDA analysis suggested that climate (temperature‐ and precipitation‐related variables) and geography had similar magnitudes of effect in shaping the distribution of SNP genotypes across the sampled range of Murray cod. Although there was poor agreement among the candidate SNP s identified by the univariate methods, the top 5% of SNP s contributing to significant RDA axes included 67% of the SNP s identified by univariate methods. We discuss the potential implications of our findings for the management of Murray cod and other species generally, particularly in relation to informing conservation actions such as translocations to improve evolutionary resilience of natural populations. Our results highlight the value of using a combination of different approaches, including polygenic methods, when testing for signatures of adaptation in landscape genomic studies.

CO 2 exchange and evapotranspiration across dryland ecosystems of southwestern North America - Joel A. Biederman; Russell L. Scott; Tom W. Bell; David R. Bowling; Sabina Dore; Jaime Garatuza‐Payan; Thomas E. Kolb; Praveena Krishnan; Dan J. Krofcheck; Marcy E. Litvak; Gregory E. Maurer; Tilden P. Meyers; et al. (Global Change Biology, 2017)
Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO 2 sink. However, such analyses are poorly constrained by measured CO 2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production ( NEP ) varying from ‐350 to +330 gC m −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP , gross ecosystem production ( GEP ), and ecosystem respiration (R eco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration ( ET ), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and R eco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS ‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO 2 exchange may be up to 3–5 times larger than current estimates.

Effects of developmental conditions on growth, stress and telomeres in black‐legged kittiwake chicks - Rebecca C. Young; Jorg Welcker; Christopher P. Barger; Scott A. Hatch; Thomas Merkling; Evgenia V. Kitaiskaia; Mark F. Haussmann; Alexander S. Kitaysky (Molecular Ecology, 2017)
Early‐life conditions can drive ageing patterns and life history strategies throughout the lifespan. Certain social, genetic and nutritional developmental conditions are more likely to produce high‐quality offspring: those with good likelihood of recruitment and productivity. Here, we call such conditions “favoured states” and explore their relationship with physiological variables during development in a long‐lived seabird, the black‐legged kittiwake ( Rissa tridactyla ). Two favoured states were experimentally generated by manipulation of food availability and brood size, while hatching order and sex were also explored as naturally generating favoured states. Thus, the favoured states we explored were high food availability, lower levels of sibling competition, hatching first and male sex. We tested the effects of favoured developmental conditions on growth, stress, telomere length (a molecular marker associated with lifespan) and nestling survival. Generation of favoured states through manipulation of both the nutritional and social environments furthered our understanding of their relative contributions to development and phenotype: increased food availability led to larger body size, reduced stress and higher antioxidant status, while lower sibling competition (social environment) led to lower telomere loss and longer telomere lengths in fledglings. Telomere length predicted nestling survival, and wing growth was also positively correlated with telomere length, supporting the idea that telomeres may indicate individual quality, mediated by favoured states.

Glutamate carboxypeptidase II (GCPII) inhibitor 2-PMPA reduces rewarding effects of the synthetic cathinone MDPV in rats: a role for N-acetylaspartylglutamate (NAAG) - Callum Hicks; Ryan A. Gregg; Sunil U. Nayak; Lee Anne Cannella; Giana J. Schena; Christopher S. Tallarida; Allen B. Reitz; Garry R. Smith; Scott M. Rawls (Psychopharmacology, 2017)

PK–PD Compass: bringing infectious diseases pharmacometrics to the patient’s bedside - Catharine C. Bulik; Justin C. Bader; Li Zhang; Scott A. Van Wart; Christopher M. Rubino; Sujata M. Bhavnani; Kim L. Sweeney; Paul G. Ambrose (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Anticipatory capacity in response to global change across an extreme elevation gradient in the Ica Basin, Peru - Rafael de Grenade; Joshua Rudow; Rossi Taboada Hermoza; Maria Elena Adauto Aguirre; Christopher A. Scott; Bram Willems; Jennifer L. Schultz; Robert G. Varady (Regional Environmental Change, 2017)

Cytotoxic activity of expanded coordination bis-thiosemicarbazones and copper complexes thereof - Fady N. Akladios; Scott D. Andrew; Christopher J. Parkinson (JBIC Journal of Biological Inorganic Chemistry, 2016)

Comparing Measures of Estuarine Ecosystem Production in a Temperate New England Estuary - Autumn Oczkowski; Christopher W. Hunt; Kenneth Miller; Candace Oviatt; Scott Nixon; Leslie Smith (Estuaries and Coasts, 2016)

Late Pleistocene climate inferences from a water balance model of Jakes Valley, Nevada (USA) - Cornelia Barth; Douglas P. Boyle; Benjamin J. Hatchett; Scott D. Bassett; Christopher B. Garner; Kenneth D. Adams (Journal of Paleolimnology, 2016)

Sigma-1 receptors modulate neonatal Nav1.5 ion channels in breast cancer cell lines - Ebru Aydar; Dan Stratton; Scott P. Fraser; Mustafa B. A. Djamgoz; Christopher Palmer (European Biophysics Journal, 2016)

Investigation of the cytotoxic implications of metal chelators against melanoma and approaches to improve the cytotoxicity profiles of metal coordinating agents - Fady N. Akladios; Scott D. Andrew; Christopher J. Parkinson (BioMetals, 2016)

Biological responses to environmental heterogeneity under future ocean conditions - Philip W. Boyd; Christopher E. Cornwall; Andrew Davison; Scott C. Doney; Marion Fourquez; Catriona L. Hurd; Ivan D. Lima; Andrew McMinn (Global Change Biology, 2016)
Organisms are projected to face unprecedented rates of change in future ocean conditions due to anthropogenic climate‐change. At present, marine life encounters a wide range of environmental heterogeneity from natural fluctuations to mean climate change. Manipulation studies suggest that biota from more variable marine environments have more phenotypic plasticity to tolerate environmental heterogeneity. Here, we consider current strategies employed by a range of representative organisms across various habitats – from short‐lived phytoplankton to long‐lived corals – in response to environmental heterogeneity. We then discuss how, if and when organismal responses (acclimate/migrate/adapt) may be altered by shifts in the magnitude of the mean climate‐change signal relative to that for natural fluctuations projected for coming decades. The findings from both novel climate‐change modelling simulations and prior biological manipulation studies, in which natural fluctuations are superimposed on those of mean change, provide valuable insights into organismal responses to environmental heterogeneity. Manipulations reveal that different experimental outcomes are evident between climate‐change treatments which include natural fluctuations vs. those which do not. Modelling simulations project that the magnitude of climate variability, along with mean climate change, will increase in coming decades, and hence environmental heterogeneity will increase, illustrating the need for more realistic biological manipulation experiments that include natural fluctuations. However, simulations also strongly suggest that the timescales over which the mean climate‐change signature will become dominant, relative to natural fluctuations, will vary for individual properties, being most rapid for CO 2 (~10 years from present day) to 4 decades for nutrients. We conclude that the strategies used by biota to respond to shifts in environmental heterogeneity may be complex, as they will have to physiologically straddle wide‐ranging timescales in the alteration of ocean conditions, including the need to adapt to rapidly rising CO 2 and also acclimate to environmental heterogeneity in more slowly changing properties such as warming.

Increased generation of intracellular reactive oxygen species initiates selective cytotoxicity against the MCF-7 cell line resultant from redox active combination therapy using copper–thiosemicarbazone complexes - Fady N. Akladios; Scott D. Andrew; Christopher J. Parkinson (JBIC Journal of Biological Inorganic Chemistry, 2016)

Population genomics of the filarial nematode parasite Wuchereria bancrofti from mosquitoes - Scott T. Small; Lisa J. Reimer; Daniel J. Tisch; Christopher L. King; Bruce M. Christensen; Peter M. Siba; James W. Kazura; David Serre; Peter A. Zimmerman (Molecular Ecology, 2016)
Wuchereria bancrofti is a parasitic nematode and the primary cause of lymphatic filariasis – a disease specific to humans. W. bancrofti currently infects over 90 million people throughout the tropics and has been acknowledged by the world health organization as a vulnerable parasite. Current research has focused primarily on the clinical manifestations of disease and little is known about the evolutionary history of W. bancrofti . To improve upon knowledge of the evolutionary history of W. bancrofti , we whole genome sequenced 13 W. bancrofti larvae. We circumvent many of the difficulties of multiple infections by sampling larvae directly from mosquitoes that were experimentally inoculated with infected blood. To begin, we used whole genome data to reconstruct the historical population size. Our results support a history of fluctuating population sizes that can be correlated with human migration and fluctuating mosquito abundances. Next, we reconstructed the putative pedigree of W. bancrofti worms within an infection using the kinship coefficient. We deduced that there are full‐sib and half‐sib relationships residing within the same larval cohort. Through combined analysis of the mitochondrial and nuclear genomes we concluded that this is likely a results of polyandrous mating, the first time reported for W. bancrofti . Lastly, we scanned the genomes for signatures of natural selection. Annotation of putative selected regions identified proteins that may have aided in a parasitic life style or may have evolved to protect against current drug treatments. We discuss our results in the greater context of understanding the biology of an animal with a unique life history and ecology.

Incorporating Resource Protection Constraints in an Analysis of Landscape Fuel-Treatment Effectiveness in the Northern Sierra Nevada, CA, USA - Christopher B. Dow; Brandon M. Collins; Scott L. Stephens (Environmental Management, 2016)

Improved cytotoxicity of pyridyl-substituted thiosemicarbazones against MCF-7 when used as metal ionophores - Fady N. Akladios; Scott D. Andrew; Christopher J. Parkinson (BioMetals, 2016)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

The Critical Role of the Cytoskeleton in the Pathogenesis of Giardia - Christopher Nosala; Scott C. Dawson (Current Clinical Microbiology Reports, 2015)

Executive summary of the 11th HHT international scientific conference - Helen Arthur; Urban Geisthoff; James R. Gossage; Christopher C. W. Hughes; Pascal Lacombe; Mary E. Meek; Paul Oh; Beth L. Roman; Scott O. Trerotola; Sebastiaan Velthuis; Whitney Wooderchak-Donahue (Angiogenesis, 2015)

Select metal and metalloid surveillance of free-ranging Eastern box turtles from Illinois and Tennessee (Terrapene carolina carolina) - Matthew C. Allender; Michael J. Dreslik; Bishap Patel; Elizabeth L. Luber; John Byrd; Christopher A. Phillips; John W. Scott (Ecotoxicology, 2015)

Improved cognition without adverse effects: novel M1 muscarinic potentiator compares favorably to donepezil and xanomeline in rhesus monkey - Joshua D. Vardigan; Christopher E. Cannon; Vanita Puri; Mandy Dancho; AmyJo Koser; Marion Wittmann; Scott D. Kuduk; John J. Renger; Jason M. Uslaner (Psychopharmacology, 2015)

Ocean and Coastal Acidification off New England and Nova Scotia - Dwight Gledhill; Meredith White; Joe Salisbury; Helmuth Thomas; Ivy Misna; Matthew Liebman; Bill Mook; Jason Grear; Allison Candelmo; R. Christopher Chambers; Christopher Gobler; Christopher Hunt; et al. (Oceanography, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Efficacy of Labeling Wetlands with Enriched 15N to Determine Amphibian Dispersal - David E. Scott; Yurena Yanes; Betsie B. Rothermel; Melissa Pilgrim; Christopher S. Romanek (Wetlands, 2015)

Monitoring the 2007 Florida east coast Karenia brevis (Dinophyceae) red tide and neurotoxic shellfish poisoning (NSP) event - Jennifer L. Wolny; Paula S. Scott; Jacob Tustison; Christopher R. Brooks (Algae, 2015)

On the Response of pH to Inorganic Nutrient Enrichment in Well-Mixed Coastal Marine Waters - Scott W. Nixon; Autumn J. Oczkowski; Michael E. Q. Pilson; Lindsey Fields; Candace A. Oviatt; Christopher W. Hunt (Estuaries and Coasts, 2015)

siRNA-Mediated Knockdown of P450 Oxidoreductase in Rats: A Tool to Reduce Metabolism by CYPs and Increase Exposure of High Clearance Compounds - Rob S. Burke; Inthirai Somasuntharam; Paul Rearden; Duncan Brown; Sujal V. Deshmukh; Martha A. DiPietro; Jillian DiMuzio; Roy Eisenhandler; Scott E. Fauty; Christopher Gibson; Marian E. Gindy; Kelly A. Hamilton; et al. (Pharmaceutical Research, 2014)

Evaluating the causal basis of ecological success within the scleractinia: an integral projection model approach - Peter J. Edmunds; Scott C. Burgess; Hollie M. Putnam; Marissa L. Baskett; Lorenzo Bramanti; Nick S. Fabina; Xueying Han; Michael P. Lesser; Joshua S. Madin; Christopher B. Wall; Denise M. Yost; Ruth D. Gates (Marine Biology, 2014)

Analysis and modeling of Nannochloropsis growth in lab, greenhouse, and raceway experiments - Patricia E. Gharagozloo; Jessica L. Drewry; Aaron M. Collins; Thomas A. Dempster; Christopher Y. Choi; Scott C. James (Journal of Applied Phycology, 2014)

A field study examining the effects of exposure to neonicotinoid seed-treated corn on commercial bumble bee colonies - G. Christopher Cutler; Cynthia D. Scott-Dupree (Ecotoxicology, 2014)

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Effects of inhibitory GABA-active neurosteroids on cocaine seeking and cocaine taking in rats - Christopher D. Schmoutz; Scott P Runyon; Nicholas E. Goeders (Psychopharmacology, 2014)

Divergence with gene flow in a population of thermophilic bacteria: a potential role for spatially varying selection - Christopher A. Wall; Gregory J. Koniges; Scott R. Miller (Molecular Ecology, 2014)
A fundamental goal of evolutionary biology is to understand how ecological diversity arises and is maintained in natural populations. We have investigated the contributions of gene flow and divergent selection to the distribution of genetic variation in an ecologically differentiated population of a thermophilic cyanobacterium ( Mastigocladus laminosus ) found along the temperature gradient of a nitrogen‐limited stream in Yellowstone National Park. For most loci sampled, gene flow appears to be sufficient to prevent substantial genetic divergence. However, one locus ( rfbC ) exhibited a comparatively low migration rate as well as other signatures expected for a gene experiencing spatially varying selection, including an excess of common variants, an elevated level of polymorphism and extreme genetic differentiation along the gradient. rfbC is part of an expression island involved in the production of the polysaccharide component of the protective envelope of the heterocyst, the specialized nitrogen‐fixing cell of these bacteria. SNP genotyping in the vicinity of rfbC revealed a ~5‐kbp region including a gene content polymorphism that is tightly associated with environmental temperature and therefore likely contains the target of selection. Two genes have been deleted both in the predominant haplotype found in the downstream region of White Creek and in strains from other Yellowstone populations of M. laminosus , which may result in the production of heterocysts with different envelope properties. This study implicates spatially varying selection in the maintenance of variation related to thermal performance at White Creek despite on‐going or recent gene flow.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Pyrogeography, historical ecology, and the human dimensions of fire regimes - Christopher I. Roos; David M. J. S. Bowman; Jennifer K. Balch; Paulo Artaxo; William J. Bond; Mark Cochrane; Carla M. D'Antonio; Ruth DeFries; Michelle Mack; Fay H. Johnston; Meg A. Krawchuk; Christian A. Kull; et al. (Journal of Biogeography, 2014)
In our 2011 synthesis (Bowman et al ., Journal of Biogeography , 2011, 38 , 2223–2236), we argued for a holistic approach to human issues in fire science that we term ‘pyrogeography’. Coughlan & Petty ( Journal of Biogeography , 2013, 40 , 1010–1012) critiqued our paper on the grounds that our ‘pyric phase’ model was built on outdated views of cultural development, claiming we developed it to be the unifying explanatory framework for all human–fire sciences. Rather, they suggest that ‘historical ecology’ could provide such a framework. We used the ‘pyric transition’ for multiple purposes but did not offer it as an exclusive explanatory framework for pyrogeography. Although ‘historical ecology’ is one of many useful approaches to studying human–fire relationships, scholars should also look to political and evolutionary ecology, ecosystems and complexity theories, as well as empirical generalizations to build an interdisciplinary fire science that incorporates human, ecological and biophysical dimensions of fire regimes.

Corrosion of metal roof materials related to volcanic ash interactions - Christopher Oze; Jim Cole; Allan Scott; Thomas Wilson; Grant Wilson; Sally Gaw; Samuel Hampton; Colin Doyle; Zhengwei Li (Natural Hazards, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Two new species of Eimeria Schneider, 1875 (Apicomplexa: Eimeriidae) from emerald tree skinks, Lamprolepis smaragdina (Lesson) (Sauria: Scincidae) from Papua New Guinea and the Philippines - Chris T. McAllister; R. Scott Seville; Donald W. Duszynski; Sarah E. Bush; Robert N. Fisher; Christopher C. Austin (Systematic Parasitology, 2013)

Organochlorine Pesticides in Squamate Reptiles from Southern Arizona, USA - Scott M. Weir; Marianne Dobrovolny; Chelsea Torres; Cassie Torres; Matt Goode; Thomas R. Rainwater; Christopher J. Salice; Todd A. Anderson (Bulletin of Environmental Contamination and Toxicology, 2013)

Pulse-based non-thermal plasma (NTP) disrupts the structural characteristics of bacterial biofilms - James R. Ferrell; Fan Shen; Scott F. Grey; Christopher J. Woolverton (Biofouling, 2013)

A standardized kudzu extract (NPI-031) reduces alcohol consumption in nontreatment-seeking male heavy drinkers - Scott E. Lukas; David Penetar; Zhaohui Su; Thomas Geaghan; Melissa Maywalt; Michael Tracy; John Rodolico; Christopher Palmer; Zhongze Ma; David Y.-W. Lee (Psychopharmacology, 2013)

Cuticular hydrocarbons as a basis for chemosensory self‐referencing in crickets: a potentially universal mechanism facilitating polyandry in insects - Carie B. Weddle; Sandra Steiger; Christopher G. Hamaker; Geoffrey D. Ower; Christopher Mitchell; Scott K. Sakaluk; John Hunt (Ecology Letters, 2013)
Females of many species obtain benefits by mating polyandrously, and often prefer novel males over previous mates. However, how do females recognise previous mates, particularly in the face of cognitive constraints? Female crickets appear to have evolved a simple but effective solution: females imbue males with their own cuticular hydrocarbons ( CHC s) at mating and utilise chemosensory self‐referencing to recognise recent mates. Female CHC profiles exhibited significant additive genetic variation, demonstrating that genetically unique chemical cues are available to support chemosensory self‐referencing. CHC profiles of males became more similar to those of females after mating, indicating physical transfer of CHC s between individuals during copulation. Experimental perfuming of males with female CHC s resulted in a female aversion to males bearing chemical cues similar to their own. Chemosensory self‐referencing, therefore, could be a widespread mechanism by which females increase the diversity of their mating partners.

Observations of below-ground characteristics of young redwood trees (Sequoia sempervirens) from two sites in New Zealand – implications for erosion control - Christopher J. Phillips; Michael Marden; Suzanne Lambie; Alex Watson; Craig Ross; Scott Fraser (Plant and Soil, 2013)

Phosphorus Uptake and Release from Submerged Sediments in a Simulated Stream Channel Inundated with a Poultry Litter Source - Christopher W. Rogers; Andrew N. Sharpley; Brian E. Haggard; J. Thad Scott (Water, Air, & Soil Pollution, 2013)

The muscarinic M1 receptor positive allosteric modulator PQCA improves cognitive measures in rat, cynomolgus macaque, and rhesus macaque - Jason M. Uslaner; Donnie Eddins; Vanita Puri; Christopher E. Cannon; Jane Sutcliffe; Chan Sing Chew; Michelle Pearson; Jeffrey A. Vivian; Ronald K. Chang; William J. Ray; Scott D. Kuduk; Marion Wittmann (Psychopharmacology, 2013)

Relationship between anthropometric factors, radiation exposure, and colon cancer incidence in the Life Span Study cohort of atomic bomb survivors - Erin O. Semmens; Kenneth J. Kopecky; Eric Grant; Robert W. Mathes; Nobuo Nishi; Hiromi Sugiyama; Hiroko Moriwaki; Ritsu Sakata; Midori Soda; Fumiyoshi Kasagi; Michiko Yamada; Saeko Fujiwara; et al. (Cancer Causes & Control, 2013)

A Short-Term Scan–Rescan Reliability Test Measuring Brain Tissue and Subcortical Hyperintensity Volumetrics Obtained Using the Lesion Explorer Structural MRI Processing Pipeline - Joel Ramirez; Christopher J. M. Scott; Sandra E. Black (Brain Topography, 2013)

Thioredoxin reductase is inhibited by the carbamoylating activity of the anticancer sulfonylhydrazine drug laromustine - Kevin P. Rice; Edmund J. Klinkerch; Scott A. Gerber; Tyler R. Schleicher; Tara J. Kraus; Christopher M. Buros (Molecular and Cellular Biochemistry, 2012)

Incorporating clonal growth form clarifies the role of plant height in response to nitrogen addition - Laura Gough; Katherine L. Gross; Elsa E. Cleland; Christopher M. Clark; Scott L. Collins; Joseph E. Fargione; Steven C. Pennings; Katharine N. Suding (Oecologia, 2012)

Detection of antibiotic resistance genes associated with methicillin-resistant Staphylococcus aureus (MRSA) and coagulase-negative staphylococci in hospital air filter dust by PCR - Christopher N. Drudge; Sigmund Krajden; Richard C. Summerbell; James A. Scott (Aerobiologia, 2012)

Conservation in a cup of water: estimating biodiversity and population abundance from environmental DNA - DAVID M. LODGE; CAMERON R. TURNER; CHRISTOPHER L. JERDE; MATTHEW A. BARNES; LINDSAY CHADDERTON; SCOTT P. EGAN; JEFFREY L. FEDER; ANDREW R. MAHON; MICHAEL E. PFRENDER (Molecular Ecology, 2012)
Three mantras often guide species and ecosystem management: (i) for preventing invasions by harmful species, ‘early detection and rapid response’; (ii) for conserving imperilled native species, ‘protection of biodiversity hotspots’; and (iii) for assessing biosecurity risk, ‘an ounce of prevention equals a pound of cure.’ However, these and other management goals are elusive when traditional sampling tools (e.g. netting, traps, electrofishing, visual surveys) have poor detection limits, are too slow or are not feasible. One visionary solution is to use an organism’s DNA in the environment (eDNA), rather than the organism itself, as the target of detection. In this issue of Molecular Ecology , Thomsen et al. (2012) provide new evidence demonstrating the feasibility of this approach, showing that eDNA is an accurate indicator of the presence of an impressively diverse set of six aquatic or amphibious taxa including invertebrates, amphibians, a fish and a mammal in a wide range of freshwater habitats. They are also the first to demonstrate that the abundance of eDNA, as measured by qPCR, correlates positively with population abundance estimated with traditional tools. Finally, Thomsen et al. (2012) demonstrate that next‐generation sequencing of eDNA can quantify species richness. Overall, Thomsen et al. (2012) provide a revolutionary roadmap for using eDNA for detection of species, estimates of relative abundance and quantification of biodiversity.

Does phylogeny matter? Assessing the impact of phylogenetic information in ecological meta‐analysis - Scott A. Chamberlain; Stephen M. Hovick; Christopher J. Dibble; Nick L. Rasmussen; Benjamin G. Van Allen; Brian S. Maitner; Jeffrey R. Ahern; Lukas P. Bell‐Dereske; Christopher L. Roy; Maria Meza‐Lopez; Juli Carrillo; Evan Siemann; et al. (Ecology Letters, 2012)
Meta‐analysis is increasingly used in ecology and evolutionary biology. Yet, in these fields this technique has an important limitation: phylogenetic non‐independence exists among taxa, violating the statistical assumptions underlying traditional meta‐analytic models. Recently, meta‐analytical techniques incorporating phylogenetic information have been developed to address this issue. However, no syntheses have evaluated how often including phylogenetic information changes meta‐analytic results. To address this gap, we built phylogenies for and re‐analysed 30 published meta‐analyses, comparing results for traditional vs. phylogenetic approaches and assessing which characteristics of phylogenies best explained changes in meta‐analytic results and relative model fit. Accounting for phylogeny significantly changed estimates of the overall pooled effect size in 47% of datasets for fixed‐effects analyses and 7% of datasets for random‐effects analyses. Accounting for phylogeny also changed whether those effect sizes were significantly different from zero in 23 and 40% of our datasets (for fixed‐ and random‐effects models, respectively). Across datasets, decreases in pooled effect size magnitudes after incorporating phylogenetic information were associated with larger phylogenies and those with stronger phylogenetic signal. We conclude that incorporating phylogenetic information in ecological meta‐analyses is important, and we provide practical recommendations for doing so.

High tolerance to abiotic stressors and invasion success of the slow growing freshwater snail, Melanoides tuberculatus - Scott M. Weir; Christopher J. Salice (Biological Invasions, 2012)

Additive effects of a cholinesterase inhibitor and a histamine inverse agonist on scopolamine deficits in humans - William Cho; Paul Maruff; John Connell; Cindy Gargano; Nicole Calder; Scott Doran; Sabrina Fox-Bosetti; Aizza Hassan; John Renger; Gary Herman; Christopher Lines; Ajay Verma (Psychopharmacology, 2011)

MicroRNA-101 Inhibits Growth of Epithelial Ovarian Cancer by Relieving Chromatin-Mediated Transcriptional Repression of p21waf1/cip1 - Assaad Semaan; Aamer M. Qazi; Shelly Seward; Sreedhar Chamala; Christopher S. Bryant; Sanjeev Kumar; Robert Morris; Christopher P. Steffes; David L. Bouwman; Adnan R Munkarah; Donald W. Weaver; Scott A. Gruber; et al. (Pharmaceutical Research, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Acute aquatic toxicity of tire and road wear particles to alga, daphnid, and fish - Christopher Marwood; Britt McAtee; Marisa Kreider; R. Scott Ogle; Brent Finley; Len Sweet; Julie Panko (Ecotoxicology, 2011)

Changing Climate, Challenging Choices: Identifying and Evaluating Climate Change Adaptation Options for Protected Areas Management in Ontario, Canada - Christopher J. Lemieux; Daniel J. Scott (Environmental Management, 2011)

Using digital time-lapse cameras to monitor species-specific understorey and overstorey phenology in support of wildlife habitat assessment - Christopher W. Bater; Nicholas C. Coops; Michael A. Wulder; Thomas Hilker; Scott E. Nielsen; Greg McDermid; Gordon B. Stenhouse (Environmental Monitoring and Assessment, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 1. Overview and Problem Formulation - Donald D. MacDonald; Dwayne R. J. Moore; Christopher G. Ingersoll; Dawn E. Smorong; R. Scott Carr; Ron Gouguet; David Charters; Duane Wilson; Tom Harris; Jon Rauscher; Susan Roddy; John Meyer (Archives of Environmental Contamination and Toxicology, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

Application of Pesticide Sprays to Fresh Produce: A Risk Assessment for Hepatitis A and Salmonella - Scott W. Stine; Inhong Song; Christopher Y. Choi; Charles P. Gerba (Food and Environmental Virology, 2011)

Functional analysis of frequently expressed Chinese rhesus macaque MHC class I molecules Mamu-A1*02601 and Mamu-B*08301 reveals HLA-A2 and HLA-A3 supertypic specificities - Scott Southwood; Christopher Solomon; Ilka Hoof; Richard Rudersdorf; John Sidney; Bjoern Peters; Angela Wahl; Oriana Hawkins; William Hildebrand; Bianca R. Mothé; Alessandro Sette (Immunogenetics, 2011)

Design, Optimization and Characterisation of Polymeric Microneedle Arrays Prepared by a Novel Laser-Based Micromoulding Technique - Ryan F. Donnelly; Rita Majithiya; Thakur Raghu Raj Singh; Desmond I. J. Morrow; Martin J. Garland; Yusuf K. Demir; Katarzyna Migalska; Elizabeth Ryan; David Gillen; Christopher J. Scott; A. David Woolfson (Pharmaceutical Research, 2011)

Numerical, Hydraulic, and Hemolytic Evaluation of an Intravascular Axial Flow Blood Pump to Mechanically Support Fontan Patients - Amy L. Throckmorton; Jugal Y. Kapadia; Steven G. Chopski; Sonya S. Bhavsar; William B. Moskowitz; Scott D. Gullquist; James J. Gangemi; Christopher M. Haggerty; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2011)

The Energy and Climate Change Implications of Different Music Delivery Methods - Christopher L. Weber; Jonathan G. Koomey; H. Scott Matthews (Journal of Industrial Ecology, 2010)
Summary The impacts of information and communications technology (ICT) on the environment have been a rich area for research in recent years. A prime example is the continuing rise of digital music delivery, which has obvious potential for reducing the energy and environmental impacts of producing and delivering music to final consumers. This study assesses the energy and carbon dioxide (CO 2 ) emissions associated with several alternative methods for delivering one album of music to a final customer, either through traditional retail or e‐commerce sales of compact discs or through a digital download service. We analyze a set of six (three compact disc and three digital download) scenarios for the delivery of one music album from the recording stage to the consumer's home in either CD or digital form. We find that despite the increased energy and emissions associated with Internet data flows, purchasing music digitally reduces the energy and carbon dioxide (CO 2 ) emissions associated with delivering music to customers by between 40% and 80% from the best‐case physical CD delivery, depending on whether a customer then burns the files to CD. Despite the dominance of the digital music delivery method, however, there are scenarios by which digital music performs less well, and these scenarios are explored. We suggest future areas of research, including alternative digital media services, such as subscription and streaming systems, for which Internet energy usage may be larger than for direct downloads.

Automating Analyses of the Distal Femur Articular Geometry Based on Three-Dimensional Surface Data - Kang Li; Scott Tashman; Freddie Fu; Christopher Harner; Xudong Zhang (Annals of Biomedical Engineering, 2010)

Factors influencing the growth and survival of larval and juvenile echinoids - Abul Kalam Azad; Scott McKinley; Christopher M. Pearce (Reviews in Aquaculture, 2010)
Many factors can influence the growth and survival of larval and juvenile echinoids (e.g. diet type, food ration, stocking density, temperature, salinity, dissolved oxygen, water chemistry and settlement cues), but most of these factors have not been studied in detail with regard to most species targeted for commercial aquaculture production. This review summarizes the state of knowledge on factors influencing the growth and survival of larval and juvenile echinoids. Sea‐urchin larvae are typically reared with either Dunaliella tertiolecta Butcher or Chaetoceros spp . The optimum food ration is in the range of 3000–9000 cells mL −1 and 20 000–60 000 cells mL −1 for D. tertiolecta and Chaetoceros spp., respectively, the concentration depending on larval stage and stocking density. Larvae have been successfully cultured at densities of 0.25–5.00 individuals mL −1 , but the optimum level appears to be 1–2 individuals mL −1 . A variety of benthic diatom species, particularly Navicula spp., can serve as the initial food source for young juveniles. Older juveniles may be fed with various species of foliose macroalgae and/or prepared diets. Most research on larval and juvenile echinoids has been done using ambient salinity and temperature, but some work has shown the importance of temperature on growth rate.

Engineered antifouling microtopographies: the role of Reynolds number in a model that predicts attachment of zoospores of Ulva and cells of Cobetia marina - Chelsea M. Magin; Christopher J. Long; Scott P. Cooper; Linnea K. Ista; Gabriel P. López; Anthony B. Brennan (Biofouling, 2010)

The most common Chinese rhesus macaque MHC class I molecule shares peptide binding repertoire with the HLA-B7 supertype - Christopher Solomon; Scott Southwood; Ilka Hoof; Richard Rudersdorf; Bjoern Peters; John Sidney; Clemencia Pinilla; Maria Cecilia Garibaldi Marcondes; Binhua Ling; Preston Marx; Alessandro Sette; Bianca R. Mothé (Immunogenetics, 2010)

Comparative genomics based on massive parallel transcriptome sequencing reveals patterns of substitution and selection across 10 bird species - AXEL KÜNSTNER; JOCHEN B. W. WOLF; NICLAS BACKSTRÖM; OSCEOLA WHITNEY; CHRISTOPHER N. BALAKRISHNAN; LAINY DAY; SCOTT V. EDWARDS; DANIEL E. JANES; BARNEY A. SCHLINGER; RICHARD K. WILSON; ERICH D. JARVIS; WESLEY C. WARREN; et al. (Molecular Ecology, 2010)
Next‐generation sequencing technology provides an attractive means to obtain large‐scale sequence data necessary for comparative genomic analysis. To analyse the patterns of mutation rate variation and selection intensity across the avian genome, we performed brain transcriptome sequencing using Roche 454 technology of 10 different non‐model avian species. Contigs from de novo assemblies were aligned to the two available avian reference genomes, chicken and zebra finch. In total, we identified 6499 different genes across all 10 species, with ∼1000 genes found in each full run per species. We found evidence for a higher mutation rate of the Z chromosome than of autosomes (male‐biased mutation) and a negative correlation between the neutral substitution rate ( d S ) and chromosome size. Analyses of the mean d N / d S ratio (ω) of genes across chromosomes supported the Hill–Robertson effect (the effect of selection at linked loci) and point at stochastic problems with ω as an independent measure of selection. Overall, this study demonstrates the usefulness of next‐generation sequencing for obtaining genomic resources for comparative genomic analysis of non‐model organisms.

Effects of nutrition on larval growth and survival in bivalves - Robert Marshall; Scott McKinley; Christopher M. Pearce (Reviews in Aquaculture, 2010)
This review examines the nutritional factors that influence the growth and survival of larval bivalves. Factors considered include feed form (live phytoplankton, preserved phytoplankton and artificial feeds) and feed biochemical composition (protein, lipid, carbohydrate and essential fatty acids). These factors, as they relate to larval production, are discussed in terms of growth and survival rates. To facilitate comparisons among larval studies, growth rates and feeding rates are standardized to common units. In addition, the standardized results for larvae of the Pacific oyster ( Crassostrea gigas Thunberg) are analysed using linear regression techniques to determine the strength of the correlations between daily doses of biochemical feed components and daily growth rates. Piecewise linear spline modelling is used to determine maximum effective dose response, the point where feeding additional biochemical components to the larvae yields no significant improvements in growth. Derived from these analyses are suggested daily rations of lipid, protein, carbohydrate, eicosapentanoic acid, docosahexanoic acid and energy for larvae of C. gigas .

Remote Detection of Marine Microbes, Small Invertebrates, Harmful Algae, and Biotoxins using the Environmental Sample Processor (ESP) - Christopher Scholin; Gregory Doucette; Scott Jensen; Brent Roman; Douglas Pargett; Roman Marin III; Christina Preston; William Jones; Jason Feldman; Cheri Everlove; Adeline Harris; Nilo Alvarado; et al. (Oceanography, 2009)

Near real‐time, autonomous detection of marine bacterioplankton on a coastal mooring in Monterey Bay, California, using rRNA‐targeted DNA probes - Christina M. Preston; Roman Marin; Scott D. Jensen; Jason Feldman; James M. Birch; Eugene I. Massion; Edward F. DeLong; Marcelino Suzuki; Kevin Wheeler; Christopher A. Scholin (Environmental Microbiology, 2009)
Summary A sandwich hybridization assay (SHA) was developed to detect 16S rRNAs indicative of phylogenetically distinct groups of marine bacterioplankton in a 96‐well plate format as well as low‐density arrays printed on a membrane support. The arrays were used in a field‐deployable instrument, the Environmental Sample Processor (ESP). The SHA employs a chaotropic buffer for both cell homogenization and hybridization, thus target sequences are captured directly from crude homogenates. Capture probes for seven of nine different bacterioplankton clades examined reacted specifically when challenged with target and non‐target 16S rRNAs derived from in vitro transcribed 16S rRNA genes cloned from natural samples. Detection limits were between 0.10–1.98 and 4.43– 12.54 fmole ml −1 homogenate for the 96‐well plate and array SHA respectively. Arrays printed with five of the bacterioplankton‐specific capture probes were deployed on the ESP in Monterey Bay, CA, twice in 2006 for a total of 25 days and also utilized in a laboratory time series study. Groups detected included marine alphaproteobacteria, SAR11, marine cyanobacteria, marine group I crenarchaea, and marine group II euryarchaea. To our knowledge this represents the first report of remote in situ DNA probe‐based detection of marine bacterioplankton.

RANK CLOCKS AND PLANT COMMUNITY DYNAMICS - Scott L. Collins; Katharine N. Suding; Elsa E. Cleland; Michael Batty; Steven C. Pennings; Katherine L. Gross; James B. Grace; Laura Gough; Joe E. Fargione; Christopher M. Clark (Ecology, 2008)
Summarizing complex temporal dynamics in communities is difficult to achieve in a way that yields an intuitive picture of change. Rank clocks and rank abundance statistics provide a graphical and analytical framework for displaying and quantifying community dynamics. We used rank clocks, in which the rank order abundance for each species is plotted over time in temporal clockwise direction, to display temporal changes in species abundances and richness. We used mean rank shift and proportional species persistence to quantify changes in community structure in long‐term data sets from fertilized and control plots in a late successional old field, frequently and infrequently burned tallgrass prairie, and Chihuahuan desert grassland and shrubland communities. Rank clocks showed that relatively constant species richness masks considerable temporal dynamics in relative species abundances. In the old field, fertilized plots initially experienced high mean rank shifts that stabilized rapidly below that of unfertilized plots. Rank shifts were higher in infrequently burned vs. annually burned tallgrass prairie and in desert grassland compared to shrubland vegetation. Proportional persistence showed that arid grasslands were more dynamic than mesic grasslands. We conclude that rank clocks and rank abundance statistics provide important insights into community dynamics that are often hidden by traditional univariate approaches.

Initial nicotine sensitivity in humans as a function of impulsivity - Kenneth A. Perkins; Caryn Lerman; Sarah B. Coddington; Christopher Jetton; Joshua L. Karelitz; John A. Scott; Annette S. Wilson (Psychopharmacology, 2008)

Immunocolloidal Targeting of the Endocytotic Siglec-7 Receptor Using Peripheral Attachment of Siglec-7 Antibodies to Poly(Lactide-co-Glycolide) Nanoparticles - Christopher J. Scott; Waleed M. Marouf; Derek J. Quinn; Richard J. Buick; Selinda J. Orr; Ryan F. Donnelly; Paul A. McCarron (Pharmaceutical Research, 2008)

Neurobehavioral effects of human immunodeficiency virus infection among former plasma donors in rural China - Robert K Heaton; Lucette A Cysique; Hua Jin; Chuan Shi; Xin Yu; Scott Letendre; Donald R Franklin; Christopher Ake; Ofilio Vigil; J Hampton Atkinson; Thomas D Marcotte; Igor Grant; et al. (Journal of NeuroVirology, 2008)

Invertebrate and microbial responses to inundation in an ephemeral river reach in New Zealand: effects of preceding dry periods - Scott T. Larned; Thibault Datry; Christopher T. Robinson (Aquatic Sciences, 2007)

Appropriation of Río San Juan water by Monterrey City, Mexico: implications for agriculture and basin water sharing - Christopher A. Scott; Francisco Flores-López; Jesús R. Gastélum (Paddy and Water Environment, 2007)

The effects of polymorphisms in genes from the renin–angiotensin, bradykinin, and fibrinolytic systems on plasma t-PA and PAI-1 levels are dependent on environmental context - Folkert W. Asselbergs; Scott M. Williams; Patricia R. Hebert; Christopher S. Coffey; Hans L. Hillege; Harold Snieder; Gerjan Navis; Douglas E. Vaughan; Wiek H. van Gilst; Jason H. Moore (Human Genetics, 2007)

Favorable balance of anti-oxidant/pro-oxidant systems and ablated oxidative stress in Brown Norway rats in renal ischemia-reperfusion injury - Vani Nilakantan; Gail Hilton; Cheryl Maenpaa; Scott K. Van Why; Galen M. Pieper; Christopher P. Johnson; Brian D. Shames (Molecular and Cellular Biochemistry, 2007)

OCCURRENCE, COMPOSITION, AND POTENTIAL FUNCTIONS OF NORTH ATLANTIC RIGHT WHALE ( EUBALAENA GLACIALIS ) SURFACE ACTIVE GROUPS - Susan E. Parks; Moira W. Brown; Lisa A. Conger; Philip K. Hamilton; Amy R. Knowlton; Scott D. Kraus; Christopher K. Slay; Peter L. Tyack (Marine Mammal Science, 2007)
Marine mammal social interactions are poorly understood primarily because of the difficulty of observing these behaviors in the wild. Observations of copulations in North Atlantic right whale surface active groups (SAGs) have led to the hypothesis that the function of these groups is for conception. The occurrence and composition of SAGs sighted from 1992 to 2001 were investigated on the basis of age, sex, and reproductive status of individuals. A total of 918 SAG events were documented. SAGs were observed in all habitat areas and in all months in which right whales were sighted. Group compositions revealed both potentially conceptive groups and nonconceptive groups. Of right whales whose age was known, 93% were first sighted in SAGs as juveniles, and more than half of all observed groups contained at least one juvenile whale. The group composition and timing of occurrence of SAGs do not support the hypothesis that all groups serve a purely conceptive function. Their functional role is likely much broader. Other potential functions include play, mating practice, or maintenance of social bonds.

Trends in solar radiation due to clouds and aerosols, southern India, 1952–1997 - Trent W. Biggs; Christopher A. Scott; Balaji Rajagopalan; Hugh N. Turral (International Journal of Climatology, 2007)
Decadal trends in cloudiness are shown to affect incoming solar radiation ( SW SFC ) in the Krishna River basin (13–20°N, 72–82°E), southern India, from 1952 to 1997. Annual average cloudiness at 14 meteorological stations across the basin decreased by 0.09% of the sky per year over 1952–1997. The decreased cloudiness partly balanced the effects of aerosols on incoming solar radiation ( SW SFC ), resulting in a small net increase in SW SFC in monsoon months (0.1–2.9 W m −2 per decade). During the non‐monsoon, aerosol forcing dominated over trends in cloud forcing, resulting in a net decrease in SW SFC (−2.8 to − 5.5 W m −2 per decade). Monthly satellite measurements from the International Satellite Cloud Climatology Project (ISCCP) covering 1983–1995 were used to screen the visual cloudiness measurements at 26 meteorological stations, which reduced the data set to 14 stations and extended the cloudiness record back to 1952. SW SFC measurements were available at only two stations, so the SW SFC record was extended in time and to the other stations using a combination of the Angstrom and Hargreaves‐Supit equations. The Hargreaves‐Supit estimates of SW SFC were then corrected for trends in aerosols using the literature values of aerosol forcing over India. Monthly values and trends in satellite measurements of SW SFC from National Aeronautics and Space Administration's (NASA's) surface radiation budget (SRB) matched the aerosol‐corrected Hargreaves‐Supit estimates over 1984–1994 (RMSE = 11.9 W m −2 , 5.2%). We conclude that meteorological station measurements of cloudiness, quality checked with satellite imagery and calibrated to local measurements of incoming radiation, provide an opportunity to extend radiation measurements in space and time. Reports of decreased cloudiness in other parts of continental Asia suggest that the cloud‐aerosol trade‐off observed in the Krishna basin may be widespread, particularly during the rainy seasons when changes in clouds have large effects on incoming radiation compared with aerosol forcing. Copyright © 2007 Royal Meteorological Society

Calibration and Evaluation of a Mercury Model for a Western Stream and Constructed Wetland - Scott Brown; Laurel Saito; Christopher Knightes; Mae Gustin (Water, Air, & Soil Pollution, 2007)

Evolutionary genetics of Carpodacus mexicanus, a recently colonized host of a bacterial pathogen, Mycoplasma gallisepticum - Christopher M. Hess; Zhenshan Wang; Scott V. Edwards (Genetica, 2007)

EphB3 receptor and ligand expression in the adult rat brain - Christopher A. Willson; Roy D. Foster; Stephen M. Onifer; Scott R. Whittemore; Jorge D. Miranda (Journal of Molecular Histology, 2006)

Remarkable Amphibian Biomass and Abundance in an Isolated Wetland: Implications for Wetland Conservation - J. WHITFIELD GIBBONS; CHRISTOPHER T. WINNE; DAVID E. SCOTT; JOHN D. WILLSON; XAVIER GLAUDAS; KIMBERLY M. ANDREWS; BRIAN D. TODD; LUKE A. FEDEWA; LUCAS WILKINSON; RIA N. TSALIAGOS; STEVEN J. HARPER; JUDITH L. GREENE; et al. (Conservation Biology, 2006)
Despite the continuing loss of wetland habitats and associated declines in amphibian populations, attempts to translate wetland losses into measurable losses to ecosystems have been lacking. We estimated the potential productivity from the amphibian community that would be compromised by the loss of a single isolated wetland that has been protected from most industrial, agricultural, and urban impacts for the past 54 years. We used a continuous drift fence at Ellenton Bay, a 10‐ha freshwater wetland on the Savannah River Site, near Aiken, South Carolina (U.S.A.), to sample all amphibians for 1 year following a prolonged drought. Despite intensive agricultural use of the land surrounding Ellenton Bay prior to 1951, we documented 24 species and remarkably high numbers and biomass of juvenile amphibians (>360,000 individuals; >1,400 kg) produced during one breeding season. Anurans (17 species) were more abundant than salamanders (7 species), comprising 96.4% of individual captures. Most (95.9%) of the amphibian biomass came from 232095 individuals of a single species of anuran (southern leopard frog [Rana sphenocephala ]). Our results revealed the resilience of an amphibian community to natural stressors and historical habitat alteration and the potential magnitude of biomass and energy transfer from isolated wetlands to surrounding terrestrial habitat. We attributed the postdrought success of amphibians to a combination of adult longevity (often >5 years), a reduction in predator abundance, and an abundance of larval food resources. Likewise, the increase of forest cover around Ellenton Bay from 60% in 2001 probably contributed to the long‐term persistence of amphibians at this site. Our findings provide an optimistic counterpoint to the issue of the global decline of biological diversity by demonstrating that conservation efforts can mitigate historical habitat degradation.

A tumor vasculature targeted liposome delivery system for combretastatin A4: Design, characterization, and in vitro evaluation - Ramakrishna Nallamothu; George C. Wood; Christopher B. Pattillo; Robert C. Scott; Mohammad F. Kiani; Bob M. Moore; Laura A. Thoma (AAPS PharmSciTech, 2006)

The Response of Ground Beetles (Coleoptera: Carabidae) to Selection Cutting in a South Carolina Bottomland Hardwood Forest - Michael D. Ulyshen; James L. Hanula; Scott Horn; John C. Kilgo; Christopher E. Moorman (Biodiversity and Conservation, 2006)

Periphyton nutrient limitation and nitrogen fixation potential along a wetland nutrient-depletion gradient - J. Thad Scott; Robert D. Doyle; Christopher T. Filstrup (Wetlands, 2005)

Aggressive basal cell carcinoma: Presentation, pathogenesis, and management - Hobart W. Walling; Scott W. Fosko; Pedram A. Geraminejad; Duane C. Whitaker; Christopher J. Arpey (Cancer and Metastasis Reviews, 2004)

Effects of Bridge Shading on Estuarine Marsh Benthic Invertebrate Community Structure and Function - Scott D. Struck; Christopher B. Craft; Stephen W. Broome; Michael D. Sanclements; John N. Sacco (Environmental Management, 2004)

The effects of scale: variation in the APOA1/C3/A4/A5 gene cluster - Andrew G. Clark; Deborah A. Nickerson; Kenneth M. Weiss; Veikko Salomaa; Eric Boerwinkle; Stephanie M. Fullerton; Anne V. Buchanan; Vibhor A. Sonpar; Jari H. Stengrd; Joshua D. Smith; Scott L. Taylor; Christopher S. Carlson (Human Genetics, 2004)

Radon fluxes in tropical forest ecosystems of Brazilian Amazonia: night‐time CO 2 net ecosystem exchange derived from radon and eddy covariance methods - Christopher S. Martens; Thomas J. Shay; Howard P. Mendlovitz; Daniel M. Matross; Scott R. Saleska; Steven C. Wofsy; W. Stephen Woodward; Mary C. Menton; José M. S. De Moura; Patrick M. Crill; Osvaldo L. L. De Moraes; Risonaldo L. Lima (Global Change Biology, 2004)
Radon‐222 (Rn‐222) is used as a transport tracer of forest canopy–atmosphere CO 2 exchange in an old‐growth, tropical rain forest site near km 67 of the Tapajós National Forest, Pará, Brazil. Initial results, from month‐long periods at the end of the wet season (June–July) and the end of the dry season (November–December) in 2001, demonstrate the potential of new Rn measurement instruments and methods to quantify mass transport processes between forest canopies and the atmosphere. Gas exchange rates yield mean canopy air residence times ranging from minutes during turbulent daytime hours to greater than 12 h during calm nights. Rn is an effective tracer for net ecosystem exchange of CO 2 (CO 2 NEE) during calm, night‐time hours when eddy covariance‐based NEE measurements are less certain because of low atmospheric turbulence. Rn‐derived night‐time CO 2 NEE (9.00±0.99 μmol m −2 s −1 in the wet season, 6.39±0.59 in the dry season) was significantly higher than raw uncorrected, eddy covariance‐derived CO 2 NEE (5.96±0.51 wet season, 5.57±0.53 dry season), but agrees with corrected eddy covariance results (8.65±1.07 wet season, 6.56±0.73 dry season) derived by filtering out lower NEE values obtained during calm periods using independent meteorological criteria. The Rn CO 2 results suggest that uncorrected eddy covariance values underestimate night‐time CO 2 loss at this site. If generalizable to other sites, these observations indicate that previous reports of strong net CO 2 uptake in Amazonian terra firme forest may be overestimated.

Effects of the Agricultural Pesticides Atrazine, Chlorothalonil, and Endosulfan on South Florida Microbial Assemblages - Holly F. Downing; Marie E. Delorenzo; Michael H. Fulton; Geoffrey I. Scott; Christopher J. Madden; John R. Kucklick (Ecotoxicology, 2004)

Identification of Differentially Expressed Transcripts from Maturing Stem of Sugarcane by in silico Analysis of Stem Expressed Sequence Tags and Gene Expression Profiling - Rosanne E. Casu; Christine M. Dimmock; Scott C. Chapman; Christopher P.L. Grof; C. Lynne McIntyre; Graham D. Bonnett; John M. Manners (Plant Molecular Biology, 2004)

Class I molecules with similar peptide-binding specificities are the result of both common ancestry and convergent evolution - Alessandro Sette; John Sidney; Brian D. Livingston; John L. Dzuris; Claire Crimi; Christopher M. Walker; Scott Southwood; Edward J. Collins; Austin L. Hughes (Immunogenetics, 2003)

Climate change and modelled biome representation in Canada's national park system: implications for system planning and park mandates - Daniel Scott; Jay R. Malcolm; Christopher Lemieux (Global Ecology and Biogeography, 2002)
Aim The study examined the potential for change in biome representation within Canada's national park system under multiple climate change scenarios and subsequent potential vulnerabilities in Parks Canada policy and planning frameworks. Location The study was conducted for Canada's 39 national parks. Methods The vegetation change scenarios were based on modelling results from the BIOME3 and MAPSS equilibrium process‐based global vegetation models (GVM), run with multiple doubled‐CO 2 climate change scenarios. The six vegetation distribution scenarios were calculated at 0.5° latitude–longitude resolution and the boundaries of 39 national parks superimposed in a geographic information system (GIS). Park management plans and other planning documents were also reviewed as part of the analysis. Results The proportional distribution of biomes in Canada's national park system was very similar (within 3% of area for each biome) using BIOME3 and MAPSS under the current climate. Regardless of the GVM and climate change scenario used, the modelling results suggest the potential for substantial change in the biome representation in Canada's national park system. In five of six vegetation scenarios, a novel biome type appeared in more than half of the national parks and greater than 50% of all vegetation grid boxes changed biome type. The proportional representation of tundra and taiga/tundra in the national park system declined in each of the vegetation scenarios, while more southerly biomes (temperate forests and savanna/woodland) increased (in some scenarios doubling to quadrupling). Results for boreal forest varied among the climate change scenarios. A range of potential vulnerabilities in existing policy and planning frameworks were identified, including the national park system plan, individual park objectives, and fire and exotic species management plans. Conclusions Climate change represents an unprecedented challenge to Parks Canada and its ability to achieve its conservation mandate as presently legislated. Research is needed not only on ecosystem responses to climate change, but also on the capacity of conservation systems and agencies to adapt to climate change.

Surface colonization of lodgepole pine (Pinus contorta var. latifolia [Dougl. Engelm.]) roots by Pseudomonas fluorescens and Paenibacillus polymyxa under gnotobiotic conditions - Elizabeth Bent; Colette Breuil; Scott Enebak; Christopher P. Chanway (Plant and Soil, 2002)

Integration of the Gene for Carboxin Resistance Does Not Impact the Ustilago maydis -Maize Interaction - Christopher N. Topp; José Ruiz-Herrera; Alfredo D. Martínez-Espinoza; Scott E. Gold (Current Microbiology, 2002)

Cloning and expression of an endocellulase gene from a novel streptomycete isolated from an East African soda lake - Pieter Solingen; Daan Meijer; Wilhelmus Kleij; Christopher Barnett; Robertus Bolle; Scott Power; Brian Jones (Extremophiles, 2001)

Demographic, landscape, and meteorological factors controlling the microbial pollution of coastal waters - Michael A. Mallin; Scott H. Ensign; Matthew R. McIver; G. Christopher Shank; Patricia K. Fowler (Hydrobiologia, 2001)

Substrate specificity of chlorophenoxyalkanoic acid-degrading bacteria is not dependent upon phylogenetically related tfdA gene types - Christopher Smejkal; Tatiana Vallaeys; Sara Burton; Hilary Lappin-Scott (Biology and Fertility of Soils, 2001)

Cryopreservation of yellow-poplar and sweetgum embryogenic cultures - Wagner A. Vendrame; Christopher P. Holliday; Paul M. Montello; Dale R. Smith; Scott A. Merkle (New Forests, 2001)

Characterization of ( R / S )‐mecoprop [2‐(2‐methyl‐4‐chlorophenoxy) propionic acid]‐degrading Alcaligenes sp. CS1 and Ralstonia sp. CS2 isolated from agricultural soils - Christopher W. Smejkal; Tatiana Vallaeys; Fabian A. Seymour; Sara K. Burton; Hilary M. Lappin‐Scott (Environmental Microbiology, 2001)
The herbicide mecoprop [2‐(2‐methyl‐4‐chlorophenoxy) propionic acid] is widely applied to corn fields in order to control broad‐leaved weeds. However, it is often detected in groundwater where it can be a persistent contaminant. Two mecoprop‐degrading bacterial strains were isolated from agricultural soils through their capability to degrade ( R/S )‐mecoprop rapidly. 16S rDNA sequencing of the isolates demonstrated that one was closely related to the genera Alcaligenes sp. (designated CS1) and the other to Ralstonia sp. (designated CS2). Additionally, these isolates demonstrated ability to grow on other related herbicides, including 2,4‐ D (2,4‐dichlorophenoxyacetic acid), MCPA [4‐chloro‐2‐methyl phenoxy acetic acid] and ( R/S )‐2,4‐DP [2‐(2,4‐dichlorophenoxy)propionic acid] as sole carbon sources. tfdABC gene‐specific probes derived from the 2,4‐ D ‐degrading Variovorax paradoxus TV1 were used in hybridization analyses to establish whether tfd ‐like genes are present in mecoprop‐degrading bacteria. Hybridization analysis demonstrated that both Alcaligenes sp. CS1 and Ralstonia sp. CS2 harboured tfdA , tfdB and tfdC genes on plasmids that have approximately > 60% sequence similarity to the tfdA , tfdB and tfdC genes of V. paradoxus . It is therefore likely that tfd ‐like genes may be involved in the degradation of mecoprop, and we are currently investigating this further.

Improvements in the Sensitivity of Time Resolved Fluorescence Energy Transfer Assays - Scott G. Jones; Denise Y. Lee; Jane F. Wright; Christopher N. Jones; Michelle L. Teear; Susan J. Gregory; D. Dougal Burns (Journal of Fluorescence, 2001)

Real-Time Data Assimilative Modeling on Georges Bank - Daniel Lynch; Christopher Naimie; Justin Ip; Craig Lewis; Francisco Werner; Richard Leuttich; Brian Blanton; John Quinlan; Dennis McGillicuddy; James Ledwell; James Churchill; Valery Kosnyrev; et al. (Oceanography, 2001)

The complete primary structure of mouse 20S proteasomes - Laura A. Elenich; D. Nandi; A. Elizabeth Kent; T. Scott McCluskey; M. Cruz; Mohan N. Iyer; Elaine C. Woodward; Christopher W. Conn; Amber L. Ochoa; David B. Ginsburg; J. J. Monaco (Immunogenetics, 1999)

Injury and short term mortality of benthic stream fishes – a comparison of collection techniques - Steven J. Cooke; Christopher M. Bunt; R. Scott McKinley (Hydrobiologia, 1998)

Spectroscopic characterization of metal binding by Klebsiella aerogenes UreE urease accessory protein - Gerard J. Colpas; Timothy G. Brayman; John McCracken; Michelle A. Pressler; Gerald T. Babcock; Li-June Ming; Christopher M. Colangelo; Robert A. Scott; R. P. Hausinger (JBIC Journal of Biological Inorganic Chemistry, 1998)

Tetrazolium reduction in acidicSphagnum-derived peat - R. Kelman Wieder; Joseph B. Yavitt; Constance E. Gasda; Scott T. Starr; Christopher J. Williams (Wetlands, 1998)

Creation and maintenance of habitat downstream from a weir for the greenside darter, Etheostoma blennioides – a rare fish in Canada - Christopher M. Bunt; Steven J. Cooke; R. Scott McKinley (Environmental Biology of Fishes, 1998)

Re-interpreting anaerobic metabolism: an argument for the application of both anaerobic glycolysis and excess post-exercise oxygen consumption (EPOC) as independent sources of energy expenditure - Christopher B. Scott (European Journal of Applied Physiology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Metabolic and performance adaptations to interval training in endurance-trained cyclists - Christopher Westgarth-Taylor; John A. Hawley; Scott Rickard; Kathryn H. Myburgh; Timothy D. Noakes; Steven C. Dennis (European Journal of Applied Physiology, 1997)

Perceptions of Species Abundance, Distribution, and Diversity: Lessons from Four Decades of Sampling on a Government-Managed Reserve - J. Whitfield Gibbons; Vincent J. Burke; Jeffrey E. Lovich; Raymond D. Semlitsch; Tracey D. Tuberville; J. Russell Bodie; Judith L. Greene; Peter H. Niewiarowski; Howard H. Whiteman; David E. Scott; Joseph H. K. Pechmann; Christopher R. Harrison; et al. (Environmental Management, 1997)